Resin composition, molded body, laminated structure, and method for producing laminated structure

By using the modified hydride (A) and the hydrogenated block copolymer (C) in the resin composition, the problem of difficult to take into account both the adhesive force and tensile elongation rate of the resin composition under low temperature conditions in the prior art is solved, and excellent adhesive force and tensile characteristics under low temperature conditions are achieved.

CN119604577APending Publication Date: 2025-03-11KURARAY CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202380055720.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-12-28
Filing Date
2023-07-25
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

It is difficult for the conventional resin composition to achieve excellent adhesive force and tensile elongation simultaneously during injection molding, especially when the adhesive force is easily reduced under low temperature conditions.

Method used

A resin composition comprising a modified hydride (A) and a resin (B) is used, wherein the modified hydride (A) contains a polymer block (A-2) of a specific vinyl bonding amount and is used in conjunction with the hydrogenated block copolymer (C) to improve the adhesion and tensile properties of the resin composition.

Benefits of technology

Under low temperature conditions, the resin composition can maintain excellent adhesion and tensile elongation, and avoid performance degradation caused by thermal deterioration.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005254009010000511
    Figure BDA0005254009010000511
  • Figure BDA0005254009010000521
    Figure BDA0005254009010000521
  • Figure BDA0005254009010000531
    Figure BDA0005254009010000531
Patent Text Reader

Abstract

A resin composition containing (A) a modified hydride of a block copolymer, which contains a polymer block (A-1) having a structural unit derived from an aromatic vinyl compound and a polymer block (A-2) having a structural unit derived from an aromatic vinyl compound, and (B) a resin, the polymer block (A-1) having a structural unit derived from an aromatic vinyl compound, the polymer block (A-2) having a structural unit derived from an aromatic vinyl compound, and the polymer block (A-1) having a structural unit derived from an aromatic vinyl compound. The polymer block (A-2) has a structural unit derived from a conjugated diene compound, the modified hydride (A) has at least one functional group selected from the group consisting of a carboxyl group, an amino group, a hydroxyl group, and a group derived from an acid anhydride, and the vinyl bonding amount of the polymer block (A-2) is 50-99 mol%; the resin (B) is at least one type selected from the group consisting of an acrylic block copolymer and a thermoplastic polyurethane resin, the mass ratio (A) / (B) of the modified hydride (A) and the resin (B) is 90 / 10-10 / 90, and the melt flow rate measured in accordance with JIS K7210: 2014 at a temperature of 230 DEG C and a load of 21 N is 5 g / 10 minutes or more.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a resin composition, a molded product, a laminated structure, and a method for producing the laminated structure. Background Art

[0002] It is known that a block copolymer having a styrene polymer block and a conjugated diene polymer block and a hydrogenated product thereof are thermoplastic and easy to mold and process, and can be used as a compatibilizer. In addition, it is also known that the block copolymer and / or its hydrogenated product are blended with a polyurethane block copolymer having a specific addition polymerization polymer block and a polyurethane block formed by a polyurethane elastomer to prepare a resin composition, thereby exhibiting melt adhesion to synthetic resins and metals (e.g., Patent Documents 1 to 3).

[0003] In order to further improve the adhesive force to synthetic resins and metals, the resin composition containing the block copolymer and / or its hydride has been improved. As one of the improvement methods, for example, a technique of using a modified polymer having a reactive functional group introduced by modifying the block copolymer and / or its hydride is known (for example, Patent Documents 4 to 6).

[0004] Prior art literature

[0005] Patent Literature

[0006] Patent Document 1: Japanese Patent Application Laid-Open No. 11-302495

[0007] Patent Document 2: Japanese Patent Application Publication No. 2003-041089

[0008] Patent Document 3: Japanese Patent Application Publication No. 2004-346109

[0009] Patent Document 4: Japanese Patent Application Publication No. 2018-024776

[0010] Patent Document 5: Japanese Patent Application Publication No. 2021-181561

[0011] Patent Document 6: International Publication No. 2021 / 215255 Summary of the invention

[0012] Problems to be solved by the invention

[0013] By using the modified polymer technology of patent documents 4 to 6, it is observed that the adhesive force to synthetic resins and metals with high polarity is improved. However, the application field of block copolymers or their hydrogenated products has expanded, and in order to be suitable for various uses, it is expected that the adhesive force is further improved. In addition, it is expected that the physical properties required as a plastic material, such as flexibility, tensile properties, and molding processability, are also excellent.

[0014] For example, in secondary molding based on injection molding, it is not easy to show excellent adhesion to both metal and synthetic resin. Specifically, the resin composition disclosed in patent document 4 needs to be injection molded at a high temperature of 260°C as described in the embodiment in order to exert excellent adhesion. However, this high temperature injection molding is likely to reduce physical properties such as tensile elongation and hue. On the other hand, when the resin composition of the prior art is injection molded at a temperature lower than 260°C (for example, about 230°C) in order to exert tensile properties such as excellent tensile elongation, the adhesion is likely to be reduced. In this case, it is desirable that the resin composition comprising the above-mentioned block copolymer and / or its hydride takes into account excellent tensile properties such as excellent adhesion and tensile elongation.

[0015] Therefore, an object of the present invention is to provide a resin composition, a molded product, a laminated structure, and a method for producing a laminated structure that are excellent in tensile properties and have strong adhesion to synthetic resins and metals.

[0016] Means used to solve problems

[0017] As a result of intensive studies to solve the above-mentioned problems, the present inventors have conceived of the present invention described below and have found that the problems can be solved.

[0018] That is, the present invention is as follows.

[0019] [1] A resin composition comprising a modified hydrogenated product of a block copolymer (A) and a resin (B), wherein the modified hydrogenated product of the block copolymer (A) comprises a polymer block (A-1) and a polymer block (A-2), wherein the polymer block (A-1) has a structural unit derived from an aromatic vinyl compound, and the polymer block (A-2) has a structural unit derived from a conjugated diene compound,

[0020] The modified hydrogenated product (A) has at least one functional group selected from a carboxyl group, an amino group, a hydroxyl group and a group derived from an acid anhydride, and the vinyl bond content of the polymer block (A-2) is 50 to 99 mol%.

[0021] The resin (B) is at least one selected from an acrylic block copolymer and a thermoplastic polyurethane resin,

[0022] The mass ratio (A) / (B) of the modified hydrogenated product (A) and the resin (B) is 90 / 10 to 10 / 90,

[0023] The resin composition has a melt flow rate of 5 g / 10 minutes or more measured at a temperature of 230° C. and a load of 21 N in accordance with JIS K7210:2014.

[0024] [2] The resin composition according to the above [1], further comprising a hydrogenated block copolymer (C), wherein the hydrogenated block copolymer (C) has a polymer block (C-1) and a polymer block (C-2), wherein the polymer block (C-1) contains a structural unit derived from an aromatic vinyl compound, and the polymer block (C-2) contains a structural unit derived from a conjugated diene compound.

[0025] [3] The resin composition according to [2] above, wherein the amount of vinyl bonds in the polymer block (C-2) is 1 to 85 mol%.

[0026] [4] The resin composition according to [2] or [3] above, wherein the hydrogenation rate of carbon-carbon double bonds in the polymer block (C-2) is 80 to 100 mol%.

[0027] [5] The resin composition according to any one of [2] to [4] above, wherein the conjugated diene compound in the polymer block (C-2) contains at least one selected from the group consisting of isoprene, butadiene and farnesene.

[0028] [6] The resin composition according to any one of [2] to [5] above, wherein the content of the polymer block (C-1) in the hydrogenated block copolymer (C) is 5 to 70% by mass.

[0029] [7] The resin composition according to any one of claims 1 to 6, wherein the content of the functional group relative to the modified hydrogenated product (A) is 0.10 to 5.00 phr.

[0030] [8] The resin composition according to any one of [1] to [7] above, wherein the hydrogenation rate of carbon-carbon double bonds in the polymer block (A-2) is 80 to 100 mol%.

[0031] [9] The resin composition according to any one of [1] to [8] above, wherein the content of the structural unit derived from isoprene in the polymer block (A-2) is 30% by mass or more.

[0032]

[10] The resin composition according to any one of [1] to [9] above, wherein the conjugated diene compound in the polymer block (A-2) contains isoprene and butadiene.

[0033]

[11] The resin composition according to any one of [1] to

[10] above, wherein the content of the polymer block (A-1) in the modified hydrogenated product (A) is 5 to 40% by mass.

[0034]

[12] The resin composition according to any one of [2] to [6] above, comprising 5 to 200 parts by mass of a softener based on 100 parts by mass of the hydrogenated block copolymer (C).

[0035]

[13] The resin composition according to

[12] above, wherein the softener is at least one selected from the group consisting of paraffinic process oil, cycloparaffinic process oil and aromatic process oil.

[0036]

[14] A molded article comprising the resin composition according to any one of [1] to

[13] above.

[0037]

[15] A laminated structure comprising a layer formed from the resin composition according to any one of [1] to

[13] above and a layer formed from a material other than the resin composition.

[0038]

[16] The laminated structure according to

[15] above, wherein the other material is at least one selected from a synthetic resin and a metal.

[0039]

[17] The method for producing a laminated structure according to

[15] or

[16] , wherein the resin composition is injection insert molded for the layer formed of a material other than the resin composition.

[0040] Effects of the Invention

[0041] According to the present invention, a resin composition, a molded product, a laminated structure, and a method for producing a laminated structure which are excellent in tensile properties and have strong adhesion to synthetic resins and metals and the like can be provided. DETAILED DESCRIPTION

[0042] Hereinafter, an example of an embodiment of the present invention will be described. However, the embodiment described below is an example for detailing the technical concept of the present invention, and the present invention is not limited to the following description.

[0043] In addition, the preferred embodiments are shown in this specification, and the combination of two or more preferred embodiments is also a preferred embodiment. Regarding matters shown in numerical ranges, when there are several numerical ranges, their lower limits and upper limits can be selectively combined as a preferred embodiment.

[0044] In addition, when there is a description of a numerical range of "XX to YY" in this specification, it means "XX or more and YY or less".

[0045] In the present specification, "(meth)acrylonitrile" means "acrylonitrile or methacrylonitrile". In addition, "(meth)acrylic acid" means "acrylic acid or methacrylic acid".

[0046] The resin composition of the present embodiment contains a modified hydrogenated product (A) and a resin (B).

[0047] The present inventors have conducted various studies on the ratio for making the tensile properties and adhesive strength of the resin composition excellent. As a result, the present inventors have found that it is effective that the modified hydrogenated product (A) contains a polymer block (A-2) having a specific vinyl bond amount. It is also found that it is effective that the resin composition contains a resin (B) and the resin (B) is at least one selected from an acrylic block copolymer and a thermoplastic polyurethane resin, and the resin composition shows a specific melt flow rate.

[0048] In the past, in order to obtain sufficient adhesive force in injection molding, a molding temperature condition of about 260°C or above is sometimes required. However, there are resin compositions that are thermally degraded due to high temperature conditions of about 260°C or above. For example, the decrease in tensile elongation and color change caused by thermal degradation may become the cause of reducing the value as a plastic material. On the other hand, when the above-mentioned resin composition is injection molded under low temperature conditions (about 230°C) that are not easy to cause a decrease in tensile elongation and color change, sufficient adhesive force cannot be obtained, and therefore, the original purpose cannot be achieved.

[0049] The resin composition of the present embodiment can exert a strong adhesive force even when injection molding is performed under low temperature (e.g., about 230°C). The reason may not be clear. As one of the reasons, it can be considered that this is because the modified hydrogenated product (A) having a reactive functional group contains a polymer block (A-2) having a specific vinyl bond amount. It can be inferred that the resin composition of the present embodiment contains a modified hydrogenated product (A) and a resin (B) containing the above-mentioned polymer block (A-2), so that the above-mentioned functional groups contained in the modified hydrogenated product (A) are present in large quantities on the molded body surface of the resin composition, and the adhesive force is improved by means of an anchoring effect. It can be considered that the above-mentioned functional groups are present in large quantities on the molded body surface of the resin composition because the vinyl bond amount of the polymer block (A-2), the resin (B), etc., have suitably played a role. It is also considered that the resin composition of the present embodiment exhibits a specific melt flow rate and can exhibit strong adhesive force even when injection-molded under low temperature conditions, and therefore can exhibit excellent tensile elongation and suppress hue change.

[0050] <Resin composition>

[0051] [Modified hydrogenated product (A)]

[0052] The modified hydrogenated product (A) comprises a polymer block (A-1) containing a structural unit derived from an aromatic vinyl compound and a polymer block (A-2) containing a structural unit derived from a conjugated diene compound.

[0053] The modified hydrogenated product (A) may be used alone or in combination of two or more.

[0054] <Polymer block (A-1)>

[0055] The polymer block (A-1) contains a structural unit derived from an aromatic vinyl compound.

[0056] From the viewpoint of mechanical strength, the lower limit of the content ratio of the structural unit derived from the aromatic vinyl compound in 100 mol% of the polymer block (A-1) is preferably 70 mol% or more, more preferably 80 mol% or more, further preferably 90 mol% or more, further preferably 95 mol% or more, and particularly preferably 100 mol%. The upper limit of the content ratio of the structural unit derived from the aromatic vinyl compound in 100 mol% of the polymer block (A-1) may be 100 mol% or less, may be less than 100 mol%, and may be 99 mol% or less, as long as the effect of the present invention is not impaired.

[0057] Examples of the aromatic vinyl compound include styrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, α-methylstyrene, β-methylstyrene, 2,6-dimethylstyrene, 2,4-dimethylstyrene, α-methyl-o-methylstyrene, α-methyl-m-methylstyrene, α-methyl-p-methylstyrene, β-methyl-o-methylstyrene, β-methyl-m-methylstyrene, β-methyl-p-methylstyrene, 2,4,6-trimethylstyrene, α-methyl-2,6-dimethylstyrene, α-methyl-2,4-dimethylstyrene, β-methyl-2,6-dimethylstyrene, β-methyl-2,4-dimethylstyrene, o-chlorostyrene, m-chlorostyrene, p-chlorostyrene, 2,6-dichlorostyrene, 2,4- dichlorostyrene, α-chloro-o-chlorostyrene, α-chloro-m-chlorostyrene, α-chloro-p-chlorostyrene, β-chloro-o-chlorostyrene, β-chloro-m-chlorostyrene, β-chloro-p-chlorostyrene, 2,4,6-trichlorostyrene, α-chloro-2,6-dichlorostyrene, α-chloro-2,4-dichlorostyrene, β-chloro-2,6-dichlorostyrene, β-chloro-2,4-dichlorostyrene, o-tert-butylstyrene, m-tert-butylstyrene, p-tert-butylstyrene, o-methoxystyrene, m-methoxystyrene, p-methoxystyrene, o-chloromethylstyrene, m-chloromethylstyrene, p-chloromethylstyrene, o-bromomethylstyrene, m-bromomethylstyrene, p-bromomethylstyrene, styrene derivatives substituted with a silyl group, indene, vinylnaphthalene, N-vinylcarbazole, etc. These aromatic vinyl compounds may be used alone or in combination of two or more.

[0058] Among them, from the viewpoint of the balance between production cost and physical properties, the aromatic vinyl compound is preferably styrene, α-methylstyrene, and p-methylstyrene, and more preferably styrene.

[0059] [Monomers other than aromatic vinyl compounds]

[0060] The polymer block (A-1) may or may not contain structural units derived from unsaturated monomers other than the aromatic vinyl compound (hereinafter sometimes referred to as "other unsaturated monomer units") unless the object and effects of the present invention are impaired.

[0061] From the viewpoint of mechanical strength, the upper limit of the content ratio of other unsaturated monomer units in 100 mol% of the polymer block (A-1) is preferably 30 mol% or less, more preferably 20 mol% or less, further preferably 10 mol% or less, further preferably 5 mol% or less, and particularly preferably 0 mol%. As long as the effect of the present invention is not impaired, the lower limit of the content ratio of other unsaturated monomer units in 100 mol% of the polymer block (A-1) may exceed 0 mol% and may be 1 mol% or more.

[0062] As other unsaturated monomers, for example, at least one selected from butadiene, isoprene, 2,3-dimethylbutadiene, 1,3-pentadiene, 1,3-hexadiene, isobutylene, methyl methacrylate, methyl vinyl ether, β-pinene, 8,9-menthene, dipentene, methylene norbornene, 2-methylenetetrahydrofuran, etc. The bonding form when the polymer block (A-1) contains other unsaturated monomer units is not particularly limited, and may be either random or tapered.

[0063] The modified hydrogenated product (A) only needs to have at least one polymer block (A-1). When the modified hydrogenated product (A) has two or more polymer blocks (A-1), these polymer blocks (A-1) may be the same or different.

[0064] It should be noted that, in this specification, "different polymer blocks" means that at least one of the monomer units constituting the polymer blocks, the weight average molecular weight, the stereoregularity, the ratio of each monomer unit when there are multiple monomer units, and the copolymerization form (random, gradient, block) is different.

[0065] (Weight Average Molecular Weight of Polymer Block (A-1))

[0066] Regarding the weight average molecular weight (Mw) of the polymer block (A-1), the weight average molecular weight of at least one polymer block (A-1) among the polymer blocks (A-1) of the modified hydrogenated product (A) is preferably 1,000 to 40,000, more preferably 2,000 to 30,000, further preferably 3,000 to 20,000, and further preferably 4,000 to 15,000. When the modified hydrogenated product (A) has at least one polymer block (A-1) having a weight average molecular weight within the above range, the mechanical strength of the resin composition is further improved, and the moldability is also easily excellent.

[0067] In addition, in this specification, the weight average molecular weight is the weight average molecular weight calculated|required by gel permeation chromatography (GPC) measurement of standard polystyrene. The detailed measurement method can be based on the method described in an Example.

[0068] (Content ratio of polymer block (A-1))

[0069] The upper limit of the content ratio of the polymer block (A-1) in 100% by mass of the modified hydrogenated product (A) is preferably 40% by mass or less, more preferably 30% by mass or less, further preferably 20% by mass or less, and further preferably 15% by mass or less. If the content ratio of the polymer block (A-1) is 40% by mass or less, the resin composition tends to show more excellent adhesion, so it is preferred. In addition, the lower limit of the content ratio of the polymer block (A-1) in 100% by mass of the modified hydrogenated product (A) is preferably 5% by mass or more, more preferably 8% by mass or more, and further preferably 10% by mass or more. If the content ratio of the polymer block (A-1) is 5% by mass or more, the resin composition tends to show more excellent tensile properties, so it is preferred.

[0070] It should be noted that in this specification, the content ratio of each polymer block in the block copolymer is expressed by 1 The value obtained by H-NMR measurement. The detailed measurement method can be based on the method described in the Examples.

[0071] <Polymer block (A-2)>

[0072] 〔Conjugated diene compounds〕

[0073] The polymer block (A-2) contains a structural unit derived from a conjugated diene compound.

[0074] From the viewpoint of tensile properties and adhesive strength of the resin composition, the lower limit of the content ratio of the structural unit derived from the conjugated diene compound in 100 mol% of the polymer block (A-2) is preferably 70 mol% or more, more preferably 80 mol% or more, further preferably 90 mol% or more, further preferably 95 mol% or more, and particularly preferably 100 mol%. As long as the effect of the present invention is not impaired, the upper limit of the content ratio of the structural unit derived from the conjugated diene compound in 100 mol% of the polymer block (A-2) can be 100 mol% or less, can be less than 100 mol%, and can be 99 mol% or less.

[0075] Examples of the conjugated diene compound include butadiene, isoprene, hexadiene, 2,3-dimethyl-1,3-butadiene, 2-phenyl-1,3-butadiene, 1,3-pentadiene, 2-methyl-1,3-pentadiene, 1,3-hexadiene, 1,3-octadiene, 1,3-cyclohexadiene, 2-methyl-1,3-octadiene, 1,3,7-octatriene, farnesene, myrcene, and chloroprene. These conjugated diene compounds may be used alone or in combination of two or more.

[0076] Among them, from the viewpoint of the resin composition having both excellent tensile properties and adhesive strength, in the polymer block (A-2), the conjugated diene compound preferably contains at least isoprene, for example, preferably contains isoprene or contains isoprene and butadiene.

[0077] In addition, from the viewpoint that the resin composition easily exhibits excellent tensile properties and adhesive strength, the lower limit of the content ratio of the structural unit derived from isoprene in 100% by mass of the polymer block (A-2) is preferably 30% by mass or more, more preferably 40% by mass or more, further preferably 45% by mass or more, and even more preferably 50% by mass or more, and may be 100% by mass.

[0078] When isoprene and butadiene are used in combination, their blending ratio [isoprene / butadiene] (mass ratio) is not particularly limited, but is preferably 5 / 95 to 95 / 5, more preferably 10 / 90 to 90 / 10, further preferably 40 / 60 to 70 / 30, and further preferably 45 / 55 to 65 / 35. In addition, when the blending ratio [isoprene / butadiene] is expressed as a molar ratio, it is preferably 5 / 95 to 95 / 5, more preferably 10 / 90 to 90 / 10, further preferably 40 / 60 to 70 / 30, and further preferably 45 / 55 to 55 / 45.

[0079] [Monomers other than conjugated diene compounds]

[0080] The polymer block (A-2) may or may not contain a structural unit derived from a polymerizable monomer other than the conjugated diene compound, unless the object and effect of the present invention are impaired.

[0081] From the viewpoint of the mechanical strength of the resin composition, the upper limit of the content ratio of the structural units derived from other polymerizable monomers in 100 mol% of the polymer block (A-2) is preferably 30 mol% or less, more preferably 20 mol% or less, further preferably 10 mol% or less, further preferably 5 mol% or less, and particularly preferably 0 mol%. As long as the effect of the present invention is not impaired, the lower limit of the content ratio of the structural units derived from other polymerizable monomers in the polymer block (A-2) may exceed 0 mol% and may be 1 mol% or more.

[0082] As other polymerizable monomers, preferred examples include aromatic vinyl compounds selected from, for example, styrene, α-methylstyrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, p-tert-butylstyrene, 2,4-dimethylstyrene, N-vinylcarbazole, vinylnaphthalene and vinylanthracene; and at least one compound selected from methyl methacrylate, methyl vinyl ether, β-pinene, 8,9-p-menthene, dipentene, methylenenorbornene, 2-methylenetetrahydrofuran, 1,3-cyclopentadiene, 1,3-cyclohexadiene, 1,3-cycloheptadiene, 1,3-cyclooctadiene and the like.

[0083] The modified hydrogenated product (A) only needs to have at least one polymer block (A-2). When the modified hydrogenated product (A) has two or more polymer blocks (A-2), these polymer blocks (A-2) may be the same or different.

[0084] (Vinyl Bond Amount of Polymer Block (A-2))

[0085] In the modified hydrogenated product (A), for example, when the structural unit constituting the polymer block (A-2) is any one of an isoprene unit and a mixture unit of isoprene and butadiene, as the bonding form of each of isoprene and butadiene, in the case of butadiene, 1,2-bonding and 1,4-bonding vinyl bonding can be presented, and in the case of isoprene, 1,2-bonding, 3,4-bonding, and 1,4-bonding vinyl bonding can be presented. Only one of these bonding forms may exist, or two or more may exist. Among them, 1,2-bonding and 3,4-bonding are set as vinyl bonding units, and the content ratio of vinyl bonding units is set as vinyl bonding amount. In this case, the content ratio of vinyl bonding units relative to the total amount of structural units derived from isoprene and / or butadiene is set as vinyl bonding amount.

[0086] In addition, in the modified hydrogenated product (A), for example, when the structural unit constituting the polymer block (A-2) includes a β-farnesene unit, the β-farnesene may present a 1,2-bond, a 1,13-bond, or a 3,13-bond. There may be only one of these bonding forms, or there may be more than two. Among them, 1,2-bond and 3,13-bond are set as vinyl bond units, in which case the content ratio of the vinyl bond unit relative to the total amount of the structural unit derived from β-farnesene is set as the vinyl bond amount.

[0087] In the modified hydrogenated product (A), for example, when the structural units constituting the polymer block (A-2) include isoprene units and / or butadiene units and include β-farnesene units, the vinyl bond amount is set to the sum of the content ratio of the vinyl bond units relative to the total amount of the structural units derived from isoprene and / or butadiene and the content ratio of the vinyl bond units relative to the total amount of the structural units derived from β-farnesene.

[0088] The vinyl bond content of the polymer block (A-2) is 50 to 99 mol%.

[0089] When the vinyl bonding amount of the polymer block (A-2) is 50 mol% or more, a strong adhesive force can be exhibited for both the synthetic resin and the metal. On the other hand, when the vinyl bonding amount of the polymer block (A-2) is 99 mol% or less, the resin composition has flexibility and can exhibit excellent tensile properties.

[0090] From the viewpoint of adhesive strength, the lower limit of the vinyl bond amount is preferably 55 mol% or more, more preferably 60 mol% or more, more preferably 65 mol% or more, further preferably 70 mol% or more, further preferably 72 mol% or more, further preferably 75 mol% or more.

[0091] From the viewpoint of flexibility and tensile properties, the upper limit of the vinyl bond amount is preferably 95 mol% or less, more preferably 90 mol% or less, further preferably 88 mol% or less, and further preferably 85 mol% or less.

[0092] In this specification, the vinyl bond amount is calculated by the method described in the examples. 1 The value was calculated by H-NMR measurement.

[0093] In the present embodiment, the vinyl bond amount can be adjusted by adjusting the type and amount of the Lewis base used as a co-catalyst (vinylating agent) during polymerization.

[0094] (Weight Average Molecular Weight of Polymer Block (A-2))

[0095] Regarding the weight average molecular weight (Mw) of the polymer block (A-2), the weight average molecular weight of at least one polymer block (A-2) among the polymer blocks (A-2) of the modified hydrogenated product (A) is preferably 50,000 to 600,000, more preferably 60,000 to 500,000, further preferably 80,000 to 400,000, and further preferably 100,000 to 300,000. By making the modified hydrogenated product (A) have at least one polymer block (A-2) having a weight average molecular weight within the above range, the tensile properties are further improved, and the resin composition is likely to exhibit excellent adhesive strength.

[0096] (Content ratio of polymer block (A-2))

[0097] The upper limit of the content ratio of the polymer block (A-2) in 100% by mass of the modified hydrogenated product (A) is preferably 95% by mass or less, more preferably 92% by mass or less, and further preferably 90% by mass or less. If the content ratio of the polymer block (A-2) in 100% by mass of the modified hydrogenated product (A) is 95% by mass or less, the resin composition is more likely to obtain excellent mechanical strength and moldability, so it is preferred. In addition, the lower limit of the content ratio of the polymer block (A-2) in the modified hydrogenated product (A) is preferably 60% by mass or more, more preferably 70% by mass or more, more preferably 80% by mass or more, and further preferably 85% by mass or more. If the content ratio of the polymer block (A-2) in 100% by mass of the modified hydrogenated product (A) is 60% by mass or more, the resin composition is more likely to show excellent adhesion, so it is preferred.

[0098] (Hydrogenation rate of polymer block (A-2))

[0099] From the viewpoint of heat resistance and weather resistance of the resin composition, the lower limit of the hydrogenation rate of the carbon-carbon double bonds in the polymer block (A-2) is preferably 80 mol% or more, more preferably 85 mol% or more, further preferably 88 mol% or more, and further preferably 90 mol% or more. The upper limit of the hydrogenation rate is not particularly limited and may be 100 mol% or less, 99.9 mol% or less, or 99.5 mol% or less.

[0100] It should be noted that in this specification, the hydrogenation rate can be measured by the polymer block before and after hydrogenation. 1 The content of carbon-carbon double bonds in the structural unit derived from the conjugated diene compound in the polymer block was determined and calculated by H-NMR measurement. Specifically, it was determined by the following formula.

[0101] Hydrogenation rate of the modified hydrogenated product (A) before modification (mol %) = {1-(the number of moles of carbon-carbon double bonds contained in the modified hydrogenated product (A) before modification) / (the number of moles of carbon-carbon double bonds contained in the modified hydrogenated product (A) before hydrogenation and before modification)}×100

[0102] More specifically, the hydrogenation rate is measured according to the method described in Examples.

[0103] (Bonding Form of Polymer Block (A-1) and Polymer Block (A-2))

[0104] As long as the polymer block (A-1) and the polymer block (A-2) are bonded, the bonding method is not limited, and can be any one of linear, branched, radial, or a combination of two or more thereof. Among them, the bonding method between the polymer block (A-1) and the polymer block (A-2) is preferably linear.

[0105] For example, when the polymer block (A-1) is represented by A and the polymer block (A-2) is represented by B, the bonding method may include a diblock copolymer represented by AB, a triblock copolymer represented by ABA or BAB, a tetrablock copolymer represented by ABAB, a pentablock copolymer represented by ABABA or BABAB, and a (AB) n Z-type copolymers (Z represents a coupling agent residue, and n represents an integer greater than 3), etc. Among them, linear triblock copolymers, pentablock copolymers or diblock copolymers are preferred, and ABA-type triblock copolymers are preferably used from the viewpoints of flexibility and ease of production.

[0106] Specific examples of the ABA type triblock copolymer include styrene-hydrogenated butadiene / isoprene-styrene copolymers, styrene-hydrogenated butadiene-styrene copolymers, and styrene-hydrogenated isoprene-styrene copolymers.

[0107] Here, in this specification, when the same polymer block is bonded into a linear shape by means of a bifunctional coupling agent, the bonded polymer block is regarded as a polymer block as a whole. Thus, including the above-mentioned examples, the polymer block that should be strictly described as YZY (Z represents a coupling residue) is shown as Y as a whole except for the case where it is necessary to distinguish it from the separate polymer block Y. In this specification, since such a polymer block containing a coupling agent residue is handled as above, for example, a block copolymer containing a coupling agent residue and strictly speaking should be described as ABZBA (Z represents a coupling agent residue) is described as ABA and handled as an example of a triblock copolymer.

[0108] (Content ratio of polymer blocks (A-1) and (A-2))

[0109] The modified hydrogenated product (A) may or may not contain other polymer blocks in addition to the polymer blocks (A-1) and (A-2) unless the object and effect of the present invention are impaired.

[0110] In the modified hydrogenated product (A) 100 mass %, the lower limit of the total content ratio of polymer block (A-1) and polymer block (A-2) is preferably 90 mass % or more, more preferably 95 mass % or more, and substantially particularly preferably 100 mass %. If it is 90 mass % or more, the resin composition is more likely to show excellent mechanical strength, moldability and adhesion, so it is preferred. In the modified hydrogenated product (A), the upper limit of the total content ratio of polymer block (A-1) and polymer block (A-2) is preferably 100 mass % or less.

[0111] 〈Functional Group〉

[0112] The modified hydrogenated product (A) has at least one functional group selected from the group consisting of a carboxyl group, an amino group, a hydroxyl group, and a group derived from an acid anhydride.

[0113] The resin composition of the present embodiment can express strong adhesive force to synthetic resin and metal by including the modified hydrogenated product (A) having the above-mentioned functional group.

[0114] The group derived from anhydride can include, for example, a group derived from maleic anhydride. Here, "a group derived from maleic anhydride" refers to a group having a structure in which one carbon of a double bond in a ring constituting maleic anhydride becomes a connecting bond. From the viewpoint of the adhesive force of the resin composition, especially the viewpoint of the adhesive force to metal, the functional group possessed by the modified hydride (A) is preferably at least one functional group selected from a carboxyl group and a group derived from anhydride, and more preferably a group derived from anhydride.

[0115] The modified hydrogenated product (A) preferably has the above functional group in the side chain, and more preferably has the above functional group in the side chain of the polymer block (A-2), thereby improving the adhesive force of the resin composition of this embodiment. It should be noted that the specific method for producing the modified hydrogenated product (A) is as follows.

[0116] The lower limit of the content of the functional group relative to the modified hydride (A) is preferably 0.10 phr or more, more preferably 0.15 phr or more, further preferably 0.20 phr or more, and further preferably 0.30 phr or more. In addition, the upper limit of the content of the functional group relative to the modified hydride (A) is preferably 5.00 phr or less, more preferably 4.00 phr or less, further preferably 3.00 phr or less, further preferably 2.00 phr or less, further preferably 1.50 phr or less, further preferably 1.00 phr or less, and can be 0.90 phr or less.

[0117] When the content of the functional group relative to the modified hydrogenated product (A) is within the above range, the adhesive force of the resin composition containing the modified hydrogenated product (A) can be easily improved, and the tensile properties become more excellent, so it is preferred. When the content of the functional group relative to the modified hydrogenated product (A) is below the upper limit of the above range, gelation can be suppressed, so it is preferred.

[0118] In addition, the content (phr) of the functional group refers to the mass parts of the functional group relative to 100 mass parts of the modified hydrogenated product (A).

[0119] The content of functional groups in the modified hydride (A) can be calculated by neutralization titration. As described above, it is a preferred embodiment that the functional group possessed by the modified hydride (A) is at least one functional group selected from a carboxyl group and a group derived from an acid anhydride. In more detail, the content of the functional group relative to the modified hydride (A) is measured according to the method described in the examples.

[0120] <Method for producing modified hydrogenated product (A)>

[0121] The modified hydrogenated product (A) can be produced by the following steps: first, at least an aromatic vinyl compound and a conjugated diene compound are used as monomers and these are polymerized to form a block copolymer; then, the block copolymer is subjected to a modification reaction using a modifier before or after hydrogenation.

[0122] (Polymerization Reaction)

[0123] The above-mentioned polymerization reaction can be carried out by, for example, solution polymerization, emulsion polymerization or solid phase polymerization. Among them, solution polymerization is preferred, and known methods such as anionic polymerization, cationic polymerization, and free radical polymerization can be applied. Among them, anionic polymerization is preferred. In the anionic polymerization method, as long as an aromatic vinyl compound and a conjugated diene compound are added successively in the presence of a solvent, an anionic polymerization initiator and a Lewis base as required to obtain a block copolymer, a coupling agent is added as required and allowed to react.

[0124] Examples of the organic lithium compound that can be used as an anionic polymerization initiator include methyl lithium, ethyl lithium, n-butyl lithium, sec-butyl lithium, tert-butyl lithium, and amyl lithium. Examples of the dilithium compound that can be used as an anionic polymerization initiator include dilithium naphthalene and dilithium hexylbenzene.

[0125] Examples of the coupling agent include dichloromethane, dibromomethane, dichloroethane, dibromoethane, dibromobenzene, phenyl benzoate, tetramethoxysilane, methyltrimethoxysilane, tetraethoxysilane, methyltriethoxysilane, 3-glycidyloxypropyltrimethoxysilane, and 3-glycidyloxypropyltriethoxysilane.

[0126] The amount of these anionic polymerization initiators and coupling agents is appropriately determined according to the desired weight average molecular weight of the modified hydride (A). Usually, anionic polymerization initiators such as organic lithium compounds and dilithium compounds are used in a ratio of 0.01 to 0.2 parts by mass relative to a total of 100 parts by mass of monomers such as aromatic vinyl compounds and conjugated diene compounds used for polymerization, and when a coupling agent is used, it is preferably used in a ratio of 0.001 to 0.8 parts by mass relative to a total of 100 parts by mass of monomers.

[0127] The solvent is not particularly limited as long as it does not adversely affect the anionic polymerization reaction, and examples thereof include aliphatic hydrocarbons such as cyclohexane, methylcyclohexane, n-hexane, and n-pentane; and aromatic hydrocarbons such as benzene, toluene, and xylene.

[0128] The polymerization reaction is usually carried out at a temperature of 0 to 100°C, preferably 10 to 70°C, for 0.5 to 50 hours, preferably 1 to 30 hours.

[0129] In addition, the amount of vinyl bonds can be increased by adding a Lewis base as a co-catalyst during the polymerization of the conjugated diene compound.

[0130] As the Lewis base that can be used, there can be listed, for example, ethers such as dimethyl ether, diethyl ether, tetrahydrofuran, 2,2-di(2-tetrahydrofuranyl)propane (DTHFP); glycol ethers such as ethylene glycol dimethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether; amines such as triethylamine, N,N,N',N'-tetramethylenediamine, N,N,N',N'-tetramethylethylenediamine, N-methylmorpholine; sodium or potassium salts of aliphatic alcohols such as sodium tert-butyrate, sodium tert-valerate or sodium isovalerate; or metal salts such as sodium or potassium salts of alicyclic alcohols such as dialkyl sodium cyclohexanoate and sodium menthate, etc. Among the above-mentioned Lewis bases, tetrahydrofuran and DTHFP are preferably used from the viewpoint of easy control of the amount of vinyl bonds. Furthermore, DTHFP is more preferably used because it can have a high vinyl bond content, can easily achieve a high hydrogenation rate without using an excessive amount of a hydrogenation catalyst, and can simultaneously achieve more excellent tensile properties and adhesive strength.

[0131] These Lewis bases may be used alone or in combination of two or more.

[0132] The amount of the Lewis base added is arbitrarily determined by controlling the amount of vinyl bonds in the polymer block (A-2). Therefore, the amount of the Lewis base added is not strictly limited, but is preferably used in a range of usually 0.1 to 1,000 mol, preferably 1 to 100 mol, per gram atom of lithium contained in the organic lithium compound or dilithium compound used as a polymerization initiator.

[0133] After the polymerization is carried out by the above method, an active hydrogen compound such as alcohols, carboxylic acids, or water is added to stop the polymerization reaction, thereby obtaining a block copolymer.

[0134] (hydrogenation)

[0135] By hydrogenating the block copolymer obtained by the above steps, a hydrogenated product of the block copolymer can be obtained.

[0136] When the block copolymer is hydrogenated, the hydrogenation reaction (hydrogenation reaction) is carried out in an inert organic solvent and in the presence of a hydrogenation catalyst. The carbon-carbon double bonds derived from the conjugated diene compound in the polymer block (A-2) in the block copolymer are hydrogenated by the hydrogenation reaction to produce a hydrogenated product of the block copolymer.

[0137] The hydrogenation reaction can be carried out at a hydrogen pressure of about 0.1 to 20 MPa, preferably 0.5 to 15 MPa, and more preferably 0.5 to 5 MPa. In addition, the hydrogenation reaction can be carried out at a reaction temperature of about 20 to 250° C., preferably 50 to 180° C., and more preferably 70 to 180° C. In addition, the hydrogenation reaction can be carried out at a reaction time of usually 0.1 to 100 hours, preferably 1 to 50 hours.

[0138] As hydrogenation catalysts, for example, Raney nickel; heterogeneous catalysts obtained by supporting metals such as Pt, Pd, Ru, Rh, and Ni on a carrier such as carbon, alumina, and diatomaceous earth; Ziegler catalysts composed of a combination of a transition metal compound and an alkyl aluminum compound, an organic lithium compound, etc.; metallocene catalysts, etc. Among them, from the viewpoint of easily suppressing the nuclear hydrogenation of an aromatic ring, a Ziegler catalyst is preferred, a Ziegler catalyst composed of a combination of a transition metal compound and an alkyl aluminum compound is more preferred, and a Ziegler catalyst composed of a combination of a nickel compound and an alkyl aluminum compound (Al / Ni-based Ziegler catalyst) is further preferred.

[0139] The hydrogenated block copolymer thus obtained can be obtained by injecting the polymerization reaction solution into methanol or the like to cause precipitation, and then heating or drying under reduced pressure; or injecting the polymerization reaction solution together with steam into hot water, performing so-called stripping to remove the solvent by azeotropy, and then heating or drying under reduced pressure.

[0140] (Modification reaction)

[0141] The modified hydrogenated product (A) can be produced by introducing the above functional groups before or after hydrogenation of the block copolymer. When the functional groups are introduced by radical reaction, it is preferred to introduce the specific functional groups after hydrogenating the block copolymer to form the hydrogenated product from the viewpoint of reaction control.

[0142] The reaction of introducing the above-mentioned functional group into the hydride to perform modification (hereinafter sometimes referred to as "modification reaction") can be performed by a known method.

[0143] The modification reaction can be carried out, for example, by dissolving the hydrogenated product of the block copolymer in an organic solvent, adding various modifiers capable of imparting the above-mentioned functional groups thereto, and reacting the mixture at about 50 to 300° C. for about 0.5 to 10 hours.

[0144] In addition, the above-mentioned modification reaction can be carried out by, for example, using an extruder without using a solvent to melt the hydrogenated block copolymer, and adding various modifiers. In this case, the temperature of the modification reaction is usually above the glass transition temperature of the hydrogenated block copolymer to below 400°C, preferably 90 to 350°C, and more preferably 100 to 300°C. The reaction time of the modification reaction is usually about 0.5 to 10 minutes.

[0145] When the modification reaction is carried out in a molten state, it is preferred to add a radical initiator, and an antioxidant may be added from the viewpoint of suppressing side reactions.

[0146] In addition, in the reaction of introducing the above-mentioned functional group to modify the block copolymer before hydrogenation, a radical initiator may be added.

[0147] From the viewpoint of easily achieving excellent workability and thermal stability, the modification reaction is preferably carried out by the latter method of performing modification in a molten state.

[0148] That is, a preferred embodiment of the method for producing the modified hydrogenated product (A) comprises the following steps: after hydrogenating the block copolymer to form a hydrogenated product, at least one functional group selected from the group consisting of a carboxyl group, an amino group, a hydroxyl group and a group derived from an acid anhydride is introduced into the hydrogenated product in a molten state using a free radical initiator.

[0149] As a modifier capable of applying the above functional group, vinylbenzyldiethylamine, vinylbenzyldimethylamine, 1-glycidyl-4-(2-pyridyl)piperazine, 1-glycidyl-4-phenylpiperazine, 1-glycidyl-4-methylpiperazine, 1-glycidyl-4-methylhomopolypiperazine, 1-glycidylhexamethyleneimine and tetraglycidyl-1,3-bisaminomethylcyclohexane, 1-dodecanol, hexadecanol (cetyl alcohol), stearyl alcohol, oleyl alcohol, etc. can be listed. In addition, as a modifier, unsaturated carboxylic acid anhydrides such as maleic anhydride, citraconic anhydride, 2,3-dimethylmaleic anhydride, and itaconic anhydride can also be used. Furthermore, a modifier capable of adding the above functional group can be adopted from the modifiers recorded in Japanese Patent Publication No. 2011-132298. The above modifier can be used alone or in combination of two or more.

[0150] The amount of the modifier added may be appropriately determined so as to achieve the desired content of the functional groups. The amount of the modifier is generally about 0.01 to 10 parts by mass, preferably 0.01 to 5 parts by mass, more preferably 0.01 to 3 parts by mass, and even more preferably 0.05 to 2 parts by mass, relative to 100 parts by mass of the block copolymer or its hydrogenated product.

[0151] As the free radical initiator, organic peroxides or organic peresters such as dialkyl peroxides, diacyl peroxides, peroxyesters, peroxyketals, dialkyl peroxides and hydroperoxides can be used, and azo compounds such as azobisisobutyronitrile and dimethylazoisobutyrate can also be used. Among the above-mentioned free radical initiators, organic peroxides are preferred, and dialkyl peroxides are more preferred.

[0152] In the modification reaction, the amount of the free radical initiator added can be appropriately determined according to the combination of the block copolymer or its hydride and the modifier. The amount of the free radical initiator is usually about 0.01 to 10 parts by mass, preferably 0.01 to 5 parts by mass, more preferably 0.01 to 3 parts by mass, and further preferably 0.05 to 2 parts by mass, relative to 100 parts by mass of the block copolymer or its hydride.

[0153] <Melt flow rate of modified hydrogenated product (A)>

[0154] The lower limit of the melt flow rate of the modified hydrogenated product (A) measured at a temperature of 230° C. and a load of 21 N according to JIS K 7210:2014 is preferably 1 g / 10 min or more, more preferably 5 g / 10 min or more, and further preferably 10 g / 10 min or more. In addition, the upper limit of the melt flow rate of the modified hydrogenated product (A) is preferably 30 g / 10 min or less, more preferably 26 g / 10 min or less, and further preferably 23 g / 10 min or less.

[0155] When the melt flow rate of the modified hydrogenated product (A) is within the above numerical range, the resin composition will be excellent in moldability and further excellent in tensile properties.

[0156] <Weight average molecular weight of modified hydrogenated product (A)>

[0157] From the viewpoint of the mechanical strength of the resin composition, the lower limit of the weight average molecular weight of the modified hydrogenated product (A) is preferably 50,000 or more, more preferably 80,000 or more, further preferably 100,000 or more, and further preferably 130,000 or more.

[0158] From the viewpoint of moldability and adhesive strength of the resin composition, the upper limit of the weight average molecular weight of the modified hydrogenated product (A) is preferably 400,000 or less, more preferably 350,000 or less, further preferably 300,000 or less, and further preferably 200,000 or less.

[0159] <Tan δ Peak Intensity and Peak Temperature of Modified Hydrogenated Product (A)>

[0160] The modified hydrogenated product (A) preferably has a tan δ peak top intensity of 1.0 to 3.0 measured under the conditions of a strain of 0.1%, a frequency of 1 Hz, a measurement temperature of -70 to +120°C, and a heating rate of 3°C / min in accordance with JIS K 7244-10:2005.

[0161] In this embodiment, the peak strength of tan δ can be measured using a test piece obtained by pressing the modified hydrogenated product (A) at 230° C. and 10 MPa for 3 minutes to prepare a 1.0 mm thick single-layer sheet and cutting the single-layer sheet into a disc shape.

[0162] It should be noted that in this embodiment, the measuring device of tan δ is not particularly limited, and a rotational rheometer "ARES-G2" (manufactured by TA Instruments) or the like can be used to test the above test piece by clamping it between a flat plate with a diameter of 8 mm. More specifically, it is as described in the Examples.

[0163] The modified hydrogenated product (A) can preferably have a lower limit of tan δ peak strength of 1.0 or more by the above measurement, and sometimes a higher value of 1.5 or more, and further 1.9 or more. In addition, the upper limit of tan δ peak strength is not particularly limited, and may be 3.0 or less, 2.5 or less, or 2.3 or less. The higher the tan δ peak strength, the better the physical properties such as vibration resistance at that temperature.

[0164] The peak top temperature of tan δ of the modified hydrogenated product (A) can be determined by the same method as that for the peak top intensity of tan δ described above.

[0165] The lower limit of the peak temperature of tan δ of the modified hydrogenated product (A) is preferably -25°C or higher, more preferably -10°C or higher, and even more preferably 0°C or higher. The upper limit of the peak temperature of tan δ may be +40°C or lower, or +35°C or lower, as long as the effect of the present invention is not impaired. When the peak temperature of tan δ of the modified hydrogenated product (A) is within the above range, the adhesive force and tensile properties of the resin composition are more likely to be excellent, which is preferred.

[0166] The peak top intensity and peak top temperature of tan δ can be controlled by optimizing the selection and content ratio of the monomers used in the modified hydrogenated product (A) or by appropriately adjusting the vinyl bond content.

[0167] <Glass transition temperature of modified hydrogenated product (A)>

[0168] The glass transition temperature of the modified hydrogenated product (A) is preferably -30 to +40°C, more preferably -20 to +30°C, and even more preferably -5 to +25°C.

[0169] When the glass transition temperature of the modified hydrogenated product (A) is within the above range, the adhesive force and tensile properties of the resin composition are likely to be more excellent, which is preferred.

[0170] In this specification, the glass transition temperature is a value measured using a differential scanning calorimeter (DSC) measuring apparatus.

[0171] [Resin (B)]

[0172] The resin (B) is at least one selected from the group consisting of acrylic block copolymers and thermoplastic polyurethane resins.

[0173] By using at least one selected from an acrylic block copolymer and a thermoplastic polyurethane resin as the resin (B), the resin composition of the present embodiment can exhibit stronger adhesion to synthetic resins and metals, etc. When the resin composition includes an acrylic block copolymer, it is preferred to use an acrylic block copolymer because the adhesion of the resin composition to metals is more significantly excellent.

[0174] 〈Acrylic block copolymer〉

[0175] The acrylic block copolymer is a copolymer having a plurality of polymer blocks, wherein the polymer blocks contain a structural unit derived from (meth)acrylate. From the viewpoint of flexibility, weather resistance, and adhesive strength, among the acrylic block copolymers, an acrylic block copolymer having a polymer block (D1) containing a structural unit derived from acrylate and a polymer block (E1) containing a structural unit derived from methacrylate is preferred.

[0176] 〔Polymer block (D1)〕

[0177] The polymer block (D1) contains a structural unit derived from acrylic acid ester. The acrylic acid ester is generally classified into a general formula of CH2=CH-COOR 1 (X)(In formula (X), R 1 represents an organic group having 1 to 3 carbon atoms) (hereinafter referred to as "acrylate (d-1)"), a general formula CH2=CH-COOR 2 (Y)(In formula (Y), R 2 represents an organic group having 4 to 12 carbon atoms) (hereinafter referred to as "acrylate (d-2)"), and acrylates other than these.

[0178] As the above R 1The organic group having 1 to 3 carbon atoms shown in the formula (d-1) may include alkyl groups having 1 to 3 carbon atoms such as methyl, ethyl, n-propyl, and isopropyl; organic groups having 1 to 3 carbon atoms in total and containing an element other than carbon such as oxygen such as methoxyethyl, hydroxyethyl, aminoethyl, and glycidyl; and the like. Examples of the acrylic acid ester (d-1) include acrylic acid esters having no functional group such as methyl acrylate, ethyl acrylate, isopropyl acrylate, and n-propyl acrylate; and acrylic acid esters having functional groups such as 2-methoxyethyl acrylate, 2-hydroxyethyl acrylate, 2-aminoethyl acrylate, and glycidyl acrylate.

[0179] As the above R 2 The organic group having 4 to 12 carbon atoms shown in the formula (a) includes, for example, alkyl groups having 4 to 12 carbon atoms, such as butyl, pentyl (amyl), hexyl, cyclohexyl, ethylhexyl, octyl, decyl, isobornyl, and lauryl; aromatic ring groups having 6 to 12 carbon atoms, such as phenyl and benzyl; and organic groups containing an element other than carbon, such as oxygen, such as ethoxyethyl, tetrahydrofurfuryl, diethylaminoethyl, and phenoxyethyl, and having a total of 4 to 12 carbon atoms. Examples of the acrylic acid ester (d-2) include acrylic acid esters having no functional group, such as n-butyl acrylate, isobutyl acrylate, sec-butyl acrylate, tert-butyl acrylate, amyl acrylate, isoamyl acrylate, n-hexyl acrylate, 2-ethylhexyl acrylate, n-octyl acrylate, isooctyl acrylate, decyl acrylate, isobornyl acrylate, lauryl acrylate, cyclohexyl acrylate, phenyl acrylate, benzyl acrylate, and the like; and acrylic acid esters having a functional group, such as 2-ethoxyethyl acrylate, 2-(diethylamino)ethyl acrylate, tetrahydrofurfuryl acrylate, 2-phenoxyethyl acrylate, and the like.

[0180] Examples of the acrylate other than the acrylate (d-1) and the acrylate (d-2) include acrylates having no functional group such as octadecyl acrylate.

[0181] Among the acrylic esters (d-1), from the viewpoint of flexibility of the obtained resin composition, acrylic esters having no functional group are preferred, methyl acrylate and ethyl acrylate are more preferred, and methyl acrylate is further preferred.

[0182] (d-1) / (D1)

[0183] The ratio of the acrylate (d-1) contained in the polymer block (D1) [(d-1) / (D1)] is preferably 10 to 100% by mass, more preferably 30 to 100% by mass, and further preferably 50 to 100% by mass. In addition, the ratio of the acrylate (d-1) contained in the polymer block (D1) may be 100% by mass. By being within the above range, the molding processability of the resin composition of the present embodiment becomes good.

[0184] The content of acrylate (d-1) and polymer block (D1) can be determined by 1 It can be determined by H-NMR, and specifically, by the method described in Examples.

[0185] Among the acrylic acid esters (d-2), in order to make the phase separation between the polymer block (D1) and the polymer block (E1) clearer and to exhibit high cohesive force when prepared as a resin composition, acrylic acid esters having no functional group are preferred, and acrylic acid alkyl esters having an alkyl group having 4 to 12 carbon atoms are more preferred, and n-butyl acrylate and 2-ethylhexyl acrylate are further preferred. In addition, n-butyl acrylate is more preferred from the viewpoint that the obtained resin composition exhibits stable durability in a wider temperature range.

[0186] The above-mentioned acrylic acid esters may be used alone or in combination of two or more. In addition, the lower limit of the content ratio of the structural unit derived from acrylic acid ester in 100% by mass of the polymer block (D1) is preferably 60% by mass or more, more preferably 80% by mass or more, further preferably 90% by mass or more, and may be 100% by mass.

[0187] Among the above acrylates, at least one selected from acrylates (d-1) and acrylates (d-2) is preferred from the viewpoint of improving the compatibility between the acrylic block copolymer and the modified hydrogenated product (A), exhibiting stable adhesive force, and achieving molding processability.

[0188] It is a preferred embodiment that the acrylic acid ester used in the polymer block (D1) comprises at least one selected from acrylic acid esters (d-1) and at least one selected from acrylic acid esters (d-2). In this case, the mass ratio (d-1) / (d-2) of the structural unit derived from the acrylic acid ester (d-1) to the structural unit derived from the acrylic acid ester (d-2) is preferably 90 / 10 to 10 / 90, more preferably 80 / 20 to 20 / 80, further preferably 70 / 30 to 30 / 70, and further preferably 60 / 40 to 40 / 60.

[0189] By making (d-1) / (d-2) within the above range, the compatibility of the acrylic block copolymer and the modified hydrogenated product (A) is improved, and stable adhesive force and molding processability are easily exhibited. It should be noted that the mass ratio of acrylate (d-1) to acrylate (d-2) can be 1 It was determined by H-NMR measurement.

[0190] As a combination of the acrylate (d-1) and the acrylate (d-2) used in the polymer block (D1), for example, methyl acrylate / n-butyl acrylate, etc., can be cited. In this case, as the acrylate (d-1) and the acrylate (d-2) used, the difference in solubility parameter between the acrylate (d-1) and the acrylate (d-2) is preferably 0.3 to 2.5 (MPa). 1 / 2 It should be noted that the solubility parameter can be calculated by the method described in "POLYMER HAND BOOK Forth Edition", VII, pages 675 to 714 (published by Wiley Interscience in 1999) and "Polymer Engineering and Science", 1974, Vol. 14, pages 147 to 154. In addition, when the acrylic block copolymer contains two or more polymer blocks (D1), the combination of acrylic esters forming these polymer blocks (D1) may be the same or different.

[0191] When the polymer block (D1) is a copolymer comprising an acrylate (d-1) unit and an acrylate (d-2) unit, it may comprise a random copolymer of acrylate (d-1) and acrylate (d-2), a block copolymer, a gradient copolymer, and it is generally desirable to comprise a random copolymer. When the acrylic block copolymer comprises more than two polymer blocks (D1), the structures of these polymer blocks (D1) may be the same or different. In addition, the lower limit of the total unit ratio of the acrylate (d-1) and (d-2) contained in the polymer block (D1) is preferably 60% by mass or more in 100% by mass of the polymer block (D1), more preferably 80% by mass or more, further preferably 90% by mass or more, and can be 100% by mass.

[0192] The glass transition temperature of the polymer block (D1) is preferably -100 to +30° C., more preferably -80 to +10° C., further preferably -70 to 0° C., and most preferably -60 to -10° C. When the glass transition temperature is within the above range, the resin composition of the present embodiment tends to have excellent adhesive strength at room temperature.

[0193] [Polymer block (E1)]

[0194] The polymer block (E1) contains a structural unit derived from a methacrylate. Examples of the methacrylate include methacrylates having no functional group such as methyl methacrylate, ethyl methacrylate, isopropyl methacrylate, n-propyl methacrylate, n-butyl methacrylate, isobutyl methacrylate, sec-butyl methacrylate, tert-butyl methacrylate, n-hexyl methacrylate, cyclohexyl methacrylate, 2-ethylhexyl methacrylate, n-octyl methacrylate, lauryl methacrylate, tridecyl methacrylate, stearyl methacrylate, isobornyl methacrylate, phenyl methacrylate, and benzyl methacrylate; and methacrylates having a functional group such as methoxyethyl methacrylate, ethoxyethyl methacrylate, diethylaminoethyl methacrylate, 2-hydroxyethyl methacrylate, 2-aminoethyl methacrylate, glycidyl methacrylate, and tetrahydrofurfuryl methacrylate.

[0195] Among these, from the viewpoint of improving the heat resistance and durability of the obtained resin composition, as polymer block (E1), it is preferably a methacrylate without functional group, more preferably methyl methacrylate, ethyl methacrylate, tert-butyl methacrylate, cyclohexyl methacrylate, 2-ethylhexyl methacrylate, isobornyl methacrylate, phenyl methacrylate, benzyl methacrylate. From the viewpoint that the phase separation of polymer block (D1) and polymer block (E1) is clearer and the mechanical strength of the obtained resin composition becomes good, as polymer block (E1), methyl methacrylate is further preferred. Polymer block (E1) can be composed of one of these methacrylates, or it can be composed of more than two. In addition, from the viewpoint of further improving mechanical strength, the above-mentioned acrylic block copolymer preferably has more than two polymer blocks (E1). In this case, these polymer blocks (E1) can be the same or different.

[0196] The peak top molecular weight (Mp) of the polymer block (E1) is not particularly limited, but is preferably in the range of 1,000 to 50,000, and more preferably in the range of 2,000 to 30,000. If the Mp of the polymer block (E1) is in the above range, there is a tendency that there is no worry about insufficient cohesion of the obtained acrylic block copolymer, the melt viscosity of the obtained acrylic block copolymer is not too high, and the productivity when manufacturing the resin composition becomes good. It should be noted that Mp refers to the molecular weight at the top position of the peak in the differential molecular weight distribution curve obtained by GPC measurement.

[0197] The lower limit of the content of the structural unit derived from methacrylate in 100% by mass of the polymer block (E1) is preferably 60% by mass or more, more preferably 80% by mass or more, further preferably 90% by mass or more, and may be 100% by mass.

[0198] The glass transition temperature of the polymer block (E1) is preferably 80 to 140° C., more preferably 90 to 130° C., and even more preferably 100 to 120° C. When the glass transition temperature is within the above range, the polymer block (E1) functions as a physical quasi-crosslinking point at the normal use temperature of the obtained resin composition, and the adhesive strength, durability, and heat resistance are likely to be excellent.

[0199] The polymer block (D1) may contain a structural unit derived from methacrylate within a range not impairing the effects of the present invention. The polymer block (E1) may contain a structural unit derived from acrylate within a range not impairing the effects of the present invention.

[0200] In addition, structural units derived from monomers other than (meth)acrylates may be contained as needed. As the other monomers, vinyl monomers with carboxyl groups such as (meth)acrylic acid, crotonic acid, maleic acid, and fumaric acid may be listed; aromatic vinyl monomers such as styrene, α-methylstyrene, p-methylstyrene, and m-methylstyrene; conjugated diene monomers such as butadiene and isoprene; olefin monomers such as ethylene, propylene, isobutylene, and octene; lactone monomers such as ε-caprolactone and valerolactone; (meth)acrylamide, (meth)acrylonitrile, maleic anhydride, vinyl acetate, vinyl chloride, vinylidene chloride, etc. When the above monomers are used, the above monomers are preferably used in an amount of 40% by mass or less, more preferably 20% by mass or less, and further preferably 10% by mass or less relative to the total mass of the monomers used in each polymer block in the acrylic block copolymer.

[0201] In the acrylic block copolymer, in addition to the polymer block (D1) and the polymer block (E1), other polymer blocks may be present as required. As the other polymer blocks, for example, polymer blocks or copolymer blocks containing structural units derived from monomers such as styrene, α-methylstyrene, p-methylstyrene, m-methylstyrene, acrylonitrile, methacrylonitrile, ethylene, propylene, isobutylene, butadiene, isoprene, octene, vinyl acetate, maleic anhydride, vinyl chloride, and vinylidene chloride can be listed; polymer blocks formed by polyethylene terephthalate, polylactic acid, polyurethane, and polydimethylsiloxane, etc. In addition, the other polymer blocks also include hydrogenated polymer blocks containing structural units derived from conjugated diene compounds such as butadiene and isoprene.

[0202] When polymer block (D1) is represented by D1, polymer blocks having a structure different from polymer block (D1) (excluding polymer block (E1)) are represented by D1', and polymer block (E1) is represented by E1, the acrylic block copolymer is preferably represented by the following general formula.

[0203] (E1-D1) n

[0204] (E1-D1) n- E1

[0205] D1-(E1-D1) n

[0206] (E1-D1) n- D1'

[0207] (E1-D1) n- Z

[0208] (D1-E1) n- Z

[0209] In the above general formula, n represents an integer of 1 to 30, Z represents a coupling site (a coupling site after a coupling agent reacts with a polymer terminal to form a chemical bond, and "-" represents a connecting bond between polymer blocks.) It should be noted that when a plurality of D1 and E1 are included in the above general formula, they may be polymer blocks of the same structure or polymer blocks of different structures.

[0210] Here, "different structures" means structures that are different in at least one of the monomer units constituting the polymer blocks, molecular weight, molecular weight distribution, stereoregularity, ratio of each monomer unit when there are multiple monomer units, and copolymerization form (random, gradient, block).

[0211] The value of n is preferably 1-15, more preferably 1-8, and even more preferably 1-4.

[0212] Among the above structures, (E1-D1) is preferred from the viewpoint of better mechanical strength of the resin composition. n 、(E1-D1) n- E1, D1-(E1-D1) n 、(E1-D1) n- The linear block copolymer represented by D1' is more preferably a diblock copolymer represented by E1-D1, a triblock copolymer represented by E1-D1-D1', and a triblock copolymer represented by E1-D1-E1 having blocks in the order of polymer block (E1), the above polymer block (D1), and the above polymer block (E1), and is further preferably a triblock copolymer represented by E1-D1-E1.

[0213] The peak top molecular weight (Mp) of the acrylic block copolymer is preferably 50,000 to 250,000. From the viewpoint of improving the fluidity of the resin composition, the Mp is more preferably 55,000 to 230,000, further preferably 60,000 to 220,000, further preferably 60,000 to 200,000, and particularly preferably 60,000 to 150,000.

[0214] The molecular weight distribution (Mw / Mn) of the acrylic block copolymer is preferably 1.00 to 1.40. From the viewpoint of excellent mechanical strength when prepared as a resin composition, Mw / Mn is more preferably 1.00 to 1.35, further preferably 1.00 to 1.30, further preferably 1.00 to 1.25, and particularly preferably 1.00 to 1.20.

[0215] It should be noted that the peak top molecular weight (Mp), number average molecular weight (Mn) and weight average molecular weight (Mw) related to the acrylic block copolymer are values ​​obtained by gel permeation chromatography and converted into standard polystyrene, and the molecular weight distribution (Mw / Mn) is a value calculated based on the above Mw and Mn values.

[0216] The mass ratio of the content of the polymer block (E1) to the content of the polymer block (D1) in the acrylic block copolymer [(E1) / (D1)] is preferably 10 / 90 to 55 / 45, more preferably 15 / 85 to 55 / 45, further preferably 20 / 80 to 53 / 47, particularly preferably 25 / 75 to 52 / 48.

[0217] The content of polymer block (D1) and polymer block (E1) can be determined by 1 It can be determined by H-NMR, and specifically, by the method described in Examples.

[0218] [Method for producing acrylic block copolymer]

[0219] The method for producing the acrylic block copolymer is not particularly limited as long as a polymer that satisfies the above conditions can be obtained, and a method based on a known method can be used. In general, as a method for obtaining a block copolymer with a narrow molecular weight distribution, a method of living polymerization of monomers forming structural units can be adopted. As such a method of living polymerization, for example, a method of living polymerization using an organic rare earth metal complex as a polymerization initiator (refer to Japanese Patent Publication No. 06-093060); a method of living anionic polymerization using an organic alkali metal compound as a polymerization initiator in the presence of an inorganic acid salt such as an alkali metal or alkaline earth metal salt (refer to Japanese Patent Publication No. 05-507737); a method of living anionic polymerization using an organic alkali metal compound as a polymerization initiator in the presence of an organic aluminum compound (refer to Japanese Patent Publication No. 11-335432); atom transfer radical polymerization (ATRP) (refer to Macromolecular Chemistry and Physics, 2000, Vol. 201, p. 1108-1114), etc.

[0220] Among the above-mentioned production methods, the method of performing living anionic polymerization using an organic alkali metal compound as a polymerization initiator in the presence of an organic aluminum compound is preferred because the transparency of the obtained block copolymer becomes high, the residual monomer is small, the odor is suppressed, and the generation of bubbles can be suppressed when the resin composition is molded. In addition, it is also preferred from the viewpoint that the molecular structure of the polymer block (E1) exhibits high syndiotacticity and has the effect of improving the heat resistance of the resin composition.

[0221] As the acrylic block copolymer, a commercially available product can be used, and specific examples thereof include "Kurarity (registered trademark)" (trade name) manufactured by Kuraray Co., Ltd. and "Nanostrength (registered trademark)" (trade name) manufactured by Arkema Co., Ltd.

[0222] 〈Thermoplastic polyurethane resin〉

[0223] The thermoplastic polyurethane resin may be obtained by reacting a polymer diol, an organic diisocyanate and a chain extender. The number average molecular weight of the polymer diol used to form the thermoplastic polyurethane resin is preferably 1,000 to 6,000. This can provide a resin composition having excellent mechanical strength, heat resistance and the like.

[0224] Here, the number average molecular weight of the polymer diol referred to in the present specification is a number average molecular weight calculated from the hydroxyl value obtained by SITE measurement in accordance with JIS K 1557-1:2007.

[0225] Examples of the polymer diol used for producing the thermoplastic polyurethane resin include polyester diol, polyether diol, polyester ether diol, polycarbonate diol, polyester polycarbonate diol, etc. These polymer diols may be used alone or in combination of two or more.

[0226] Examples of the polyester diol used for producing the thermoplastic polyurethane resin include polyester diols obtained by reacting at least one dicarboxylic acid component selected from aliphatic dicarboxylic acids, aromatic dicarboxylic acids and their esters with a low molecular weight diol; polyester diols obtained by ring-opening polymerization of lactones, and the like. More specifically, the polyester diols include, for example, polyester diols obtained by polycondensing at least one of aliphatic dicarboxylic acids having 6 to 12 carbon atoms, such as glutaric acid, adipic acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, and dodecanedioic acid; aromatic dicarboxylic acids, such as terephthalic acid, isophthalic acid, and phthalic acid, and their esters, and at least one of aliphatic diols having 2 to 10 carbon atoms, such as ethylene glycol, propylene glycol, 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, 1,9-nonanediol, 3-methyl-1,5-pentanediol, and 2-methyl-1,8-octanediol, polycaprolactone diol, and polyvalerolactone diol.

[0227] Examples of the polyether diol used for producing the thermoplastic polyurethane resin include polyethylene glycol, polypropylene glycol, and polytetramethylene glycol.

[0228] Examples of the polycarbonate diol used for producing the thermoplastic polyurethane resin include polycarbonate diols obtained by reacting at least one aliphatic diol such as 1,4-butanediol, 1,5-pentanediol, 1,6-hexanediol, and 1,8-octanediol with a carbonate such as diphenyl carbonate or an alkyl carbonate, or phosgene.

[0229] The organic diisocyanate used for producing the thermoplastic polyurethane resin is not particularly limited, and is preferably at least one selected from aromatic diisocyanates, alicyclic diisocyanates, and aliphatic diisocyanates having a molecular weight of 500 or less. Specific examples of the organic diisocyanate include 4,4'-diphenylmethane diisocyanate, toluene diisocyanate, p-phenylene diisocyanate, xylylene diisocyanate, naphthalene diisocyanate, hydrogenated 4,4'-diphenylmethane diisocyanate (4,4'-dicyclohexylmethane diisocyanate), isophorone diisocyanate, hexamethylene diisocyanate, and the like, and among these, 4,4'-diphenylmethane diisocyanate is preferred.

[0230] As a chain extender for manufacturing thermoplastic polyurethane resin, any chain extender used in the manufacture of thermoplastic polyurethane resin can be used, and its type is not particularly limited. Among them, the chain extender is preferably selected from at least one of aliphatic diols, alicyclic diols and aromatic diols. As specific examples of chain extenders, diols such as ethylene glycol, diethylene glycol, 1,4-butanediol, 1,5-pentanediol, 2-methyl-1,3-propanediol, 1,6-hexanediol, neopentyl glycol, 1,9-nonanediol, cyclohexanediol, and 1,4-bis(β-hydroxyethoxy)benzene can be listed. Among these, aliphatic diols having 2 to 6 carbon atoms are preferred, and 1,4-butanediol is more preferred. These chain extenders can be used alone or in combination of two or more.

[0231] The thermoplastic polyurethane resin is preferably a thermoplastic polyurethane resin obtained by reacting a polymer diol, a chain extender, and an organic diisocyanate in a range of mole number of polymer diol: mole number of chain extender = 1: 0.2 to 8, and [total mole number of polymer diol and chain extender]: [mole number of organic diisocyanate] = 1: 0.98 to 1.04. As a result, when the resin composition of the present embodiment is melt-molded by extrusion molding, injection molding, etc., the melt viscosity does not increase sharply, and the target molded article, laminated structure, etc. can be smoothly manufactured, and the heat resistance of the obtained product becomes good.

[0232] The hardness (type A hardness; measured at 25°C) of the thermoplastic polyurethane resin is preferably 55 to 95. When the hardness of the thermoplastic polyurethane resin is 55 or more, the mechanical strength of the molded article, laminated structure, etc. obtained from the resin composition becomes good. In addition, when the hardness of the thermoplastic polyurethane resin is 95 or less, the softness of the molded article, laminated structure, etc. obtained from the resin composition becomes high.

[0233] The method for producing the thermoplastic polyurethane resin is not particularly limited, and the resin can be produced by any of the prepolymer method and the one-step method using the above-mentioned high molecular weight diol, organic diisocyanate and chain extender by utilizing a known urethanization reaction. Among these, it is preferred to carry out melt polymerization in the substantial absence of a solvent, and it is more preferred to produce the resin by continuous melt polymerization using a multi-screw extruder.

[0234] As thermoplastic polyurethane resin, commercially available products can be used. As specific examples, "Elastollan (registered trademark)" (trade name) manufactured by BASF Polyurethane Elastomers, "Miractran (registered trademark)" (trade name) manufactured by Nippon Miractran, "RESAMINE P" (trade name) manufactured by Dainichi Seika Industries, "U-Fine (registered trademark) P" (trade name) manufactured by Asahi Glass Co., Ltd., etc. can be listed.

[0235] [Hydrogenated block copolymer (C)]

[0236] The resin composition of the present embodiment preferably contains a hydrogenated block copolymer (C) from the viewpoint of maintaining excellent tensile properties and strong adhesive force and making it easier to adjust hardness.

[0237] The hydrogenated block copolymer (C) comprises a polymer block (C-1) containing a structural unit derived from an aromatic vinyl compound and a polymer block (C-2) containing a structural unit derived from a conjugated diene compound.

[0238] In addition, the hydrogenated block copolymer (C) is a resin of a different type from the modified hydrogenated product (A). The hydrogenated block copolymer (C) preferably does not have a carboxyl group, an amino group, a hydroxyl group, and a group derived from an acid anhydride. The hydrogenated block copolymer (C) may contain any one of an epoxy group, a silanol group, an aldehyde group, a carbonyl group, a nitro group, a cyano group, and an ether bond.

[0239] The hydrogenated block copolymer (C) may be used alone or in combination of two or more.

[0240] 〈Polymer block (C-1)〉

[0241] 〔Aromatic vinyl compounds〕

[0242] The polymer block (C-1) contains a structural unit derived from an aromatic vinyl compound.

[0243] The structural units constituting the polymer block (C-1), the content ratio of the structural units, and the types of compounds from which the structural units are derived are the same as those of the polymer block (A-1).

[0244] (Weight Average Molecular Weight of Polymer Block (C-1))

[0245] The weight average molecular weight (Mw) of the polymer block (C-1) is not particularly limited, but the weight average molecular weight of at least one polymer block (C-1) among the polymer blocks (C-1) of the hydrogenated block copolymer (C) is preferably 3,000 to 80,000, more preferably 4,000 to 70,000, further preferably 5,000 to 60,000, and further preferably 6,000 to 50,000. When the hydrogenated block copolymer (C) has at least one polymer block (C-1) having a weight average molecular weight within the above range, the mechanical strength of the resin composition is further improved, and the moldability is also easily excellent.

[0246] (Content ratio of polymer block (C-1))

[0247] The upper limit of the content ratio of the polymer block (C-1) in 100% by mass of the hydrogenated block copolymer (C) is preferably 70% by mass or less, more preferably 65% ​​by mass or less, further preferably 40% by mass or less, and further preferably 35% by mass or less. If the content ratio of the polymer block (C-1) is 70% by mass or less, the resin composition tends to show moderate flexibility, so it is preferred. In addition, the lower limit of the content ratio of the polymer block (C-1) in 100% by mass of the hydrogenated block copolymer (C) is preferably 5% by mass or more, more preferably 10% by mass or more, and further preferably 15% by mass or more. If the content ratio of the polymer block (C-1) is 5% by mass or more, the mechanical strength such as the tensile elongation of the resin composition tends to be further improved, so it is preferred.

[0248] 〈Polymer block (C-2)〉

[0249] 〔Conjugated diene compounds〕

[0250] The polymer block (C-2) contains a structural unit derived from a conjugated diene compound.

[0251] The structural units constituting the polymer block (C-2), the content ratio of the structural units, and the types of compounds from which the structural units are derived are the same as those of the polymer block (A-2).

[0252] On the other hand, from the viewpoint of the balance between production cost and physical properties, the conjugated diene compound in the polymer block (C-2) is preferably at least one selected from the group consisting of isoprene, butadiene and farnesene.

[0253] When isoprene and butadiene are used in combination, the blending ratio [isoprene / butadiene] (mass ratio) thereof is not particularly limited, but is preferably 5 / 95 to 95 / 5, more preferably 10 / 90 to 90 / 10, further preferably 40 / 60 to 70 / 30, and further preferably 45 / 55 to 65 / 35. In addition, when the blending ratio [isoprene / butadiene] is expressed as a molar ratio, it is preferably 5 / 95 to 95 / 5, more preferably 10 / 90 to 90 / 10, further preferably 20 / 80 to 80 / 20, further preferably 30 / 70 to 70 / 30, further preferably 40 / 60 to 70 / 30, and further preferably 45 / 55 to 55 / 45.

[0254] (Vinyl Bond Amount of Polymer Block (C-2))

[0255] The bonding form of the conjugated diene compound is not particularly limited as long as the effects of the present invention are not impaired.

[0256] In the hydrogenated block copolymer (C), for example, when the structural unit constituting the polymer block (C-2) is any one of an isoprene unit and a mixture unit of isoprene and butadiene, as the bonding form of each of isoprene and butadiene, in the case of butadiene, 1,2-bonding and 1,4-bonding vinyl bonding can be presented, and in the case of isoprene, 1,2-bonding, 3,4-bonding, and 1,4-bonding vinyl bonding can be presented. Only one of these bonding forms may exist, or two or more may exist. Among them, 1,2-bonding and 3,4-bonding are set as vinyl bonding units, and the content ratio of vinyl bonding units is set as the vinyl bonding amount. In this case, the content ratio of the vinyl bonding unit relative to the total amount of the structural units derived from isoprene and / or butadiene is set as the vinyl bonding amount.

[0257] In addition, in the hydrogenated block copolymer (C), for example, when the structural unit constituting the polymer block (C-2) is a β-farnesene unit, 1,2-bonding, 1,13-bonding, and 3,13-bonding may be present. There may be only one of these bonding forms, or there may be more than two. Among them, 1,2-bonding and 3,13-bonding are set as vinyl bonding units, and the content ratio of the vinyl bonding unit is set as the vinyl bonding amount. In this case, the content ratio of the vinyl bonding unit relative to the total amount of the structural unit derived from β-farnesene is set as the vinyl bonding amount.

[0258] In the modified hydrogenated product (A), for example, when the structural units constituting the polymer block (C-2) include isoprene units and / or butadiene units and include β-farnesene units, the vinyl bond amount is set to the sum of the content ratio of the vinyl bond units relative to the total amount of the structural units derived from isoprene and / or butadiene and the content ratio of the vinyl bond units relative to the total amount of the structural units derived from β-farnesene.

[0259] The lower limit of the vinyl bond content of the polymer block (C-2) is preferably 1 mol% or more, more preferably 3 mol% or more, further preferably 5 mol% or more, and further preferably 6 mol% or more. If the lower limit of the vinyl bond content in the polymer block (C-2) is 1 mol% or more, the resin composition tends to exhibit more excellent tensile properties, so it is preferred.

[0260] In addition, the upper limit of the vinyl bonding amount in polymer block (C-2) is preferably 85 mol% or less, more preferably 75 mol% or less, further preferably 65 mol% or less, further preferably 55 mol% or less, particularly preferably 45 mol% or less. In the case of attaching importance to realizing excellent bonding strength by improving the flexibility of resin composition, improving the adhesion with adherend, the upper limit of the vinyl bonding amount in polymer block (C-2) is more particularly preferably 35 mol% or less, further particularly preferably 30 mol% or less, most preferably 25 mol% or less. If the vinyl bonding amount in polymer block (C-2) is 85 mol% or less, resin composition easily shows more excellent flexibility, so it is preferred.

[0261] The hydrogenated block copolymer (C) can be used alone or in combination. For example, in the case of using a molded body formed by the resin composition of the present embodiment under a low temperature environment, or in the case of requiring high impact resistance for the molded body, it is preferred to use at least one hydrogenated block copolymer (C) containing a polymer block (C-2) having a low vinyl bond content. The vinyl bond content in the polymer block (C-2) having a low vinyl bond content is preferably 1 to 30 mol%, more preferably 3 to 20 mol%, and further preferably 5 to 10 mol%.

[0262] (Weight Average Molecular Weight of Polymer Block (C-2))

[0263] The weight average molecular weight (Mw) of the polymer block (C-2) was determined by gel permeation chromatography (GPC).

[0264] Regarding the weight average molecular weight (Mw) of the polymer block (C-2), the weight average molecular weight of at least one polymer block (C-2) among the polymer blocks (C-2) of the hydrogenated block copolymer (C) is preferably 30,000 to 600,000, more preferably 40,000 to 500,000, further preferably 45,000 to 450,000, and further preferably 50,000 to 400,000. It is preferred that the hydrogenated block copolymer (C) has at least one polymer block (C-2) having a weight average molecular weight within the above range, because the tensile properties of the resin composition are further improved and the adhesive strength is also easily excellent.

[0265] (Content ratio of polymer block (C-2))

[0266] The upper limit of the content ratio of the polymer block (C-2) in 100% by mass of the hydrogenated block copolymer (C) is preferably 95% by mass or less, more preferably 90% by mass or less, and further preferably 85% by mass or less. If the content ratio of the polymer block (C-2) is 95% by mass or less, the resin composition easily exhibits excellent mechanical strength and moldability, so it is preferred. In addition, the lower limit of the content ratio of the polymer block (C-2) in 100% by mass of the hydrogenated block copolymer (C) is preferably 30% by mass or more, more preferably 45% by mass or more, more preferably 60% by mass or more, and further preferably 70% by mass or more. If the content ratio of the polymer block (C-2) is 30% by mass or more, the resin composition easily exhibits excellent flexibility, so it is preferred.

[0267] (Hydrogenation rate of polymer block (C-2))

[0268] From the viewpoint of heat resistance and weather resistance of the resin composition, the lower limit of the hydrogenation rate of the carbon-carbon double bonds in the polymer block (C-2) is preferably 80 mol% or more, more preferably 85 mol% or more, further preferably 88 mol% or more, and further preferably 90 mol% or more. The upper limit of the hydrogenation rate is not particularly limited, and may be 100 mol% or less, 99.9 mol% or less, or 99.5 mol% or less. The hydrogenation rate of the carbon-carbon double bonds in the polymer block (C-2) can be determined by utilizing the hydrogenation of the polymer block before and after hydrogenation. 1 The H-NMR measurement was performed to obtain and calculate. Specifically, it was obtained by the following formula.

[0269] Hydrogenation rate of hydrogenated block copolymer (C) (mol %) = {1-(the number of moles of carbon-carbon double bonds contained per 1 mole of hydrogenated block copolymer (C)) / (the number of moles of carbon-carbon double bonds contained per 1 mole of hydrogenated block copolymer (C) before hydrogenation)}×100

[0270] (Bonding method of polymer block (C-1) and polymer block (C-2))

[0271] The bonding method between the polymer block (C-1) and the polymer block (C-2) is the same as the bonding method between the polymer block (A-1) and the polymer block (A-2) described above.

[0272] (Content ratio of polymer blocks (C-1) and (C-2))

[0273] The hydrogenated block copolymer (C) may or may not contain other polymer blocks in addition to the polymer blocks (C-1) and (C-2) unless the object and effect of the present invention are impaired.

[0274] In the hydrogenated block copolymer (C) 100 mass%, the lower limit of the total content of polymer block (C-1) and polymer block (C-2) is preferably 90 mass% or more, more preferably 95 mass% or more, and particularly preferably substantially 100 mass%. If the above content is 90 mass% or more, the resin composition is easy to have excellent mechanical strength and moldability, so it is preferred. In the hydrogenated block copolymer (C), the upper limit of the total content of polymer block (C-1) and polymer block (C-2) is preferably 100 mass% or less.

[0275] <Method for producing hydrogenated block copolymer (C)>

[0276] The hydrogenated block copolymer (C) can be produced by using at least an aromatic vinyl compound and a conjugated diene compound as monomers, performing a polymerization reaction to obtain a block copolymer, and then hydrogenating the obtained block copolymer.

[0277] The block copolymer can be produced by the same method as the method for producing the block copolymer in the method for producing the modified hydrogenated product (A). The hydrogenation method is also the same as the hydrogenation method in the method for producing the modified hydrogenated product (A).

[0278] <Weight average molecular weight of hydrogenated block copolymer (C)>

[0279] From the viewpoint of the mechanical strength of the resin composition, the lower limit of the weight average molecular weight of the hydrogenated block copolymer (C) is preferably 50,000 or more, more preferably 60,000 or more, further preferably 70,000 or more, and further preferably 100,000 or more.

[0280] From the viewpoint of moldability of the resin composition, the upper limit of the weight average molecular weight of the hydrogenated block copolymer (C) is preferably 500,000 or less, more preferably 450,000 or less, and even more preferably 400,000 or less.

[0281] <Tan δ Peak Intensity and Peak Temperature of Hydrogenated Block Copolymer (C)>

[0282] The hydrogenated block copolymer (C) preferably has a tan δ peak top intensity of 0.05 to 3.0 measured under the conditions of a strain of 0.1%, a frequency of 1 Hz, a measurement temperature of -70 to +120°C, and a heating rate of 3°C / min in accordance with JIS K 7244-10:2005.

[0283] The peak top intensity of tan δ of the hydrogenated block copolymer (C) can be measured in the same manner as described for the modified hydrogenated product (A).

[0284] The hydrogenated block copolymer (C) has a peak strength of tan δ of 0.3 or more as measured above, and a higher value of 1.0 or more, and further a value of 2.0 or more. In addition, the upper limit of the peak strength of tan δ is not particularly limited, and may be 2.5 or less. The higher the peak strength of tan δ, the better the physical properties such as vibration resistance at that temperature.

[0285] The lower limit of the peak temperature of tan δ of the hydrogenated block copolymer (C) is preferably -65°C or higher, more preferably -60°C or higher, and further preferably -55°C or higher. The upper limit of the peak temperature of tan δ may be +20°C or lower, or +10°C or lower, as long as the effect of the present invention is not impaired. When the peak temperature of tan δ of the hydrogenated block copolymer (C) is within the above range, the resin composition can more easily obtain sufficient adhesive force and tensile properties under actual use environment, which is preferred.

[0286] The peak top intensity and peak top temperature of tan δ of the hydrogenated block copolymer (C) can be controlled by optimizing the selection and content ratio of the monomers used in the hydrogenated block copolymer (C) or by appropriately adjusting the vinyl bond content.

[0287] <Glass transition temperature of hydrogenated block copolymer (C)>

[0288] The glass transition temperature of the hydrogenated block copolymer (C) is preferably -70 to +20°C, more preferably -65 to +10°C, and even more preferably -60 to +5°C.

[0289] When the glass transition temperature of the hydrogenated block copolymer (C) is within the above range, the resin composition is more likely to obtain sufficient adhesive force and tensile properties under actual use environment, which is preferred.

[0290] [Content of each ingredient]

[0291] The mass ratio (A) / (B) of the modified hydrogenated product (A) and the resin (B) is 90 / 10 to 10 / 90.

[0292] If the mass ratio (A) / (B) is within the above numerical range, both tensile properties and adhesive strength are excellent. From the viewpoint of easily exerting more excellent tensile properties and strong adhesive strength, the mass ratio (A) / (B) is more preferably 80 / 20 to 10 / 90, further preferably 70 / 30 to 10 / 90, further preferably 60 / 40 to 10 / 90, further preferably 55 / 45 to 10 / 90.

[0293] When the resin composition of the present embodiment contains a hydrogenated block copolymer (C), from the viewpoint of easily exerting a stronger adhesive force, the lower limit of the content of the hydrogenated block copolymer (C) is preferably 20 parts by mass or more, more preferably 50 parts by mass or more, and even more preferably 70 parts by mass or more relative to 100 parts by mass of the content of the modified hydrogenated product (A).

[0294] When the resin composition of the present embodiment contains a hydrogenated block copolymer (C), the upper limit of the content of the hydrogenated block copolymer (C) is preferably 1000 parts by mass or less, more preferably 800 parts by mass or less, and even more preferably 700 parts by mass or less, relative to 100 parts by mass of the content of the modified hydrogenated product (A), from the viewpoint of easily exhibiting more excellent tensile properties.

[0295] When the resin composition of the present embodiment contains a hydrogenated block copolymer (C), from the viewpoint of easily exerting a stronger adhesive force, the lower limit of the content of the hydrogenated block copolymer (C) is preferably 10 parts by mass or more, more preferably 20 parts by mass or more, and even more preferably 40 parts by mass or more relative to 100 parts by mass of the content of the resin (B).

[0296] When the resin composition of the present embodiment contains a hydrogenated block copolymer (C), the upper limit of the content of the hydrogenated block copolymer (C) is preferably 300 parts by mass or less, more preferably 200 parts by mass or less, and even more preferably 150 parts by mass or less, based on 100 parts by mass of the content of the resin (B), from the viewpoint of easily exhibiting more excellent tensile properties.

[0297] From the viewpoint that the resin composition tends to exhibit stronger adhesive force, the lower limit of the content of the modified hydrogenated product (A) in 100% by mass of the resin composition is preferably 5% by mass or more, more preferably 8% by mass or more, and even more preferably 12% by mass or more.

[0298] From the viewpoint of stably obtaining both good adhesive force and tensile properties, the upper limit of the content of the modified hydrogenated product (A) in 100% by mass of the resin composition is preferably 70% by mass or less, more preferably 60% by mass or less, and even more preferably 50% by mass or less.

[0299] When the hydrogenated block copolymer (C) and the softener described below are not contained, the total content ratio of the modified hydrogenated product (A) and the resin (B) in 100% by mass of the resin composition is preferably 95% by mass or more, more preferably 99% by mass or more, and further preferably 99.5% by mass or more, and the upper limit may be 100% by mass or less.

[0300] When no softener described below is contained, the total content of the modified hydrogenated product (A), the resin (B) and the hydrogenated block copolymer (C) in 100% by mass of the resin composition is preferably 95% by mass or more, more preferably 99% by mass or more, and further preferably 99.5% by mass or more, and the upper limit may be 100% by mass or less.

[0301] When a softener described later is included, the total content of the modified hydrogenated product (A), the resin (B), the hydrogenated block copolymer (C) and the softener in 100% by mass of the resin composition is preferably 95% by mass or more, more preferably 99% by mass or more, and further preferably 99.5% by mass or more, and the upper limit may be 100% by mass or less.

[0302] [Softener]

[0303] The resin composition of the present embodiment may not contain a softener. On the other hand, from the viewpoint that the resin composition is more likely to show excellent moldability and flexibility, the resin composition of the present embodiment may contain a softener. The softener is preferably used when the resin composition contains a hydrogenated block copolymer (C). The softener may also be used when the resin composition does not contain a hydrogenated block copolymer (C).

[0304] The softener may be a softener commonly used in rubber and plastic. Examples of the softener include paraffinic, cycloparaffinic, and aromatic process oils; phthalic acid derivatives such as dioctyl phthalate and dibutyl phthalate; white oil; mineral oil; liquid copolymers of ethylene and α-olefins; liquid paraffin; polybutene; and low molecular weight polyisobutylene.

[0305] From the viewpoint of compatibility between the modified hydrogenated product (A) and the resin (B) or the viewpoint of compatibility between both the modified hydrogenated product (A) and the hydrogenated block copolymer (C) and the resin (B), the softener is preferably at least one selected from the group consisting of paraffinic process oils, cycloparaffinic process oils and aromatic process oils.

[0306] When the resin composition contains a hydrogenated block copolymer (C) and a softener, from the viewpoint of the molding processability of the resin composition, the lower limit of the content of the softener is preferably 5 parts by mass or more, more preferably 30 parts by mass or more, further preferably 50 parts by mass or more, and further preferably 80 parts by mass or more, relative to 100 parts by mass of the content of the hydrogenated block copolymer (C). In addition, from the viewpoint of avoiding the oozing out of the softener from the resin composition, the upper limit of the content of the softener is preferably 200 parts by mass or less, more preferably 150 parts by mass or less, and further preferably 120 parts by mass or less, relative to 100 parts by mass of the content of the hydrogenated block copolymer (C).

[0307] [additive]

[0308] The resin composition of the present embodiment may contain additives within the range that does not impair the effects of the present invention. Specifically, additives may be contained in addition to the modified hydrogenated product (A) and the resin (B), additives may be contained in addition to the modified hydrogenated product (A), the resin (B) and the hydrogenated block copolymer (C), additives may be contained in addition to the modified hydrogenated product (A), the resin (B) and the softener, and additives may be contained in addition to the modified hydrogenated product (A), the resin (B), the hydrogenated block copolymer (C) and the softener.

[0309] Examples of additives include thermoplastic polymers other than the modified hydrogenated product (A), the resin (B) and the hydrogenated block copolymer (C), antioxidants, inorganic fillers, adhesiveness-imparting resins, light stabilizers, processing aids, flame retardants, antistatic agents, matting agents, anti-blocking agents, ultraviolet absorbers, mold release agents, foaming agents, antibacterial agents, antifungal agents, fragrances, pigments, colorants such as pigments, and the like.

[0310] The additives may be used alone or in combination of two or more.

[0311] 〈Antioxidants〉

[0312] The resin composition of the present embodiment preferably further contains an antioxidant.

[0313] Examples of the antioxidant include hindered phenol-based, phosphorus-based, lactone-based, and hydroxy-based antioxidants, etc. Among these, hindered phenol-based antioxidants are preferred.

[0314] When an antioxidant is contained, the content of the antioxidant is preferably within a range in which coloring does not occur when the resin composition is melt-kneaded. The content of the antioxidant is preferably 0.001 to 5 parts by mass relative to 100 parts by mass of the total content of the modified hydrogenated product (A), the resin (B) and the hydrogenated block copolymer (C). It should be noted that when the resin composition of the present embodiment does not contain the hydrogenated block copolymer (C), the content of the antioxidant is preferably 0.001 to 5 parts by mass relative to 100 parts by mass of the total content of the modified hydrogenated product (A) and the resin (B).

[0315] [Method for producing resin composition]

[0316] The method for producing the resin composition of the present embodiment is not particularly limited, and the resin composition can be produced by any method as long as it is a method that can mix the modified hydrogenated product (A) and the resin (B), the hydrogenated block copolymer (C) that can be used as needed, a softener and additives, and can be produced by known means.

[0317] For example, the components of the resin composition can be mixed and manufactured by using a mixer such as a Henschel mixer, a V-blender, a ribbon blender, a drum blender, a cone blender, etc. In addition, after the mixing, the components can be melt-mixed at about 80 to 350 ° C using a mixer such as a single screw extruder, a twin screw extruder, a kneader, a Banbury mixer, a roller, etc. From the viewpoint of easily making the components of the resin composition compatible, it is preferably a melt mixing method.

[0318] [Melt flow rate of resin composition]

[0319] The resin composition has a melt flow rate of 5 g / 10 min or more measured at a temperature of 230° C. and a load of 21 N in accordance with JIS K7210:2014. If the resin composition has a melt flow rate of 5 g / 10 min or more, it has flexibility, can obtain excellent tensile properties, and tends to have excellent adhesive strength. In addition, the resin composition also has good moldability.

[0320] From the viewpoint of achieving more excellent tensile properties and adhesive strength, the lower limit of the melt flow rate of the resin composition is preferably 10 g / 10 min or more, more preferably 20 g / 10 min or more, and even more preferably 30 g / 10 min or more.

[0321] From the viewpoint of tensile properties and moldability, the upper limit of the melt flow rate of the resin composition is preferably 200 g / 10 min or less, more preferably 150 g / 10 min or less, and even more preferably 100 g / 10 min or less.

[0322] As a method for adjusting the melt flow rate of the resin composition to the above range, preferred examples include: a method of appropriately setting the blending amounts of the modified hydrogenated product (A) and the resin (B), and the hydrogenated block copolymer (C) used as needed; a method of adjusting the degree of polymerization of each resin component used in the resin composition; and a method of adjusting the type of monomer used in each resin component.

[0323] [Tensile elongation at break]

[0324] The resin composition of the present embodiment has a tensile elongation at break measured in accordance with ISO 37:2017 of preferably 220 to 800%, more preferably 300 to 800%, further preferably 400 to 750%, and further preferably 500 to 700%.

[0325] When the tensile elongation at break of the resin composition is within the above numerical range, the adhesive force is more excellent, which is preferred.

[0326] The tensile elongation at break can be measured according to the method described in Examples.

[0327] [Tensile breaking strength]

[0328] For the resin composition of the present embodiment, the lower limit of the tensile strength at break measured according to ISO37:2017 is preferably 1.0 MPa or more, more preferably 1.5 MPa or more, and further preferably 2.0 MPa or more. In addition, the upper limit of the tensile strength at break of the resin composition of the present embodiment is not particularly limited, and for example, it may be 200 MPa or less.

[0329] When the tensile strength at break of the resin composition is within the above numerical range, the adhesive force is more excellent, which is preferred.

[0330] The tensile strength at break can be measured according to the method described in Examples.

[0331] [Peel strength]

[0332] For the resin composition of the present embodiment, the peel strength measured according to JIS K 6854-2:1999 is preferably 5N / 25mm or more, more preferably 10N / 25mm or more, and further preferably 15N / 25mm or more. In addition, the upper limit of the tensile strength at break of the resin composition of the present embodiment is not particularly limited, and for example, it can be 200N / 25mm or less.

[0333] When the peel strength with respect to the resin composition is within the above numerical range, it is preferable because it is an adhesive force that can be used in practical applications.

[0334] The peel strength can be measured according to the method described in Examples.

[0335] Regarding the resin composition described in this embodiment, the above peel strength relative to the synthetic resin is preferably 5N / 25mm or more. Regarding the resin composition described in this embodiment, the above peel strength relative to aluminum as a metal is preferably 3N / 25mm or more, and more preferably 5N / 25mm or more. Regarding the resin composition described in this embodiment, the above peel strength relative to SUS as a metal is preferably 3N / 25mm or more, and more preferably 5N / 25mm or more.

[0336] <Molding>

[0337] The resin composition of the present embodiment can be made into various molded bodies by melt-kneading molding machine. In addition, the resin composition of the present embodiment can be made into various molded bodies by injection molding, injection compression molding, extrusion molding, blow molding, compression molding, vacuum forming and foaming molding, etc. after the resin composition is made into bales, crumbs or pellets, etc.

[0338] From the viewpoint of achieving both excellent tensile properties and adhesive strength, the molding temperature of the resin composition, specifically, the cylinder temperature of the extruder during injection molding or extrusion molding, is preferably 160 to 250° C., more preferably 180 to 230° C. The cylinder temperature may be appropriately set as long as the effects of the present invention are not excessively impaired.

[0339] The shape, structure, use, etc. of the molded article containing the resin composition of the present embodiment are not particularly limited. On the other hand, the resin composition of the present embodiment has excellent tensile properties and has strong adhesion to synthetic resins and metals, so the resin composition of the present embodiment can be suitably used as a part of a laminated structure.

[0340] [Tensile elongation at break]

[0341] The molded article containing the resin composition of the present embodiment has a tensile elongation at break measured in accordance with ISO 37:2017 of preferably 220 to 800%, more preferably 300 to 800%, further preferably 400 to 750%, and further preferably 500 to 700%.

[0342] When the tensile elongation at break of the resin composition is within the above numerical range, the adhesive force is more excellent, which is preferred.

[0343] The tensile elongation at break can be measured according to the method described in Examples.

[0344] [Tensile breaking strength]

[0345] The lower limit of the tensile strength at break of the molded body containing the resin composition of the present embodiment measured according to ISO37:2017 is preferably 1.0 MPa or more, more preferably 1.5 MPa or more, and further preferably 2.0 MPa or more. In addition, the upper limit of the tensile strength at break of the molded body containing the resin composition of the present embodiment is not particularly limited, for example, it can be 200 MPa or less.

[0346] When the tensile strength at break of the molded article containing the resin composition is within the above numerical range, the adhesive force is more excellent, which is preferred.

[0347] The tensile strength at break can be measured according to the method described in Examples.

[0348] [Peel strength]

[0349] The peel strength of the molded body containing the resin composition of the present embodiment measured according to JIS K 6854-2:1999 is preferably 5N / 25mm or more, more preferably 10N / 25mm or more, and further preferably 15N / 25mm or more. In addition, the upper limit of the tensile strength at break of the molded body containing the resin composition of the present embodiment is not particularly limited, and for example, may be 200N / 25mm or less.

[0350] When the peel strength of the molded article containing the resin composition is within the above numerical range, it is an adhesive strength that can be used in practical applications and is therefore preferred.

[0351] The peel strength can be measured according to the method described in Examples.

[0352] The above-mentioned peel strength of the molded body containing the resin composition of this embodiment with respect to synthetic resin is preferably 5N / 25mm or more. With respect to the resin composition described in this embodiment, the above-mentioned peel strength with respect to aluminum as a metal is preferably 3N / 25mm or more, and more preferably 5N / 25mm or more. With respect to the resin composition described in this embodiment, the above-mentioned peel strength with respect to SUS as a metal is preferably 3N / 25mm or more, and more preferably 5N / 25mm or more.

[0353] <Laminated structure>

[0354] The laminated structure has a layer formed of the resin composition of the present embodiment and a layer formed of another material other than the resin composition (hereinafter referred to as “other layer”).

[0355] The above-mentioned laminated structure may have multiple layers as long as it has at least one layer formed by the resin composition and other layers. In addition, when the laminated structure has multiple other layers, the multiple other layers may be layers formed by the same material or layers formed by different materials.

[0356] The resin composition of the present embodiment exhibits strong adhesive force. Therefore, in the laminated structure, the layer formed of the resin composition of the present embodiment serves as an adhesive layer, and the other layers serve as adherends.

[0357] The material constituting the other layers that become the adherend can be listed as synthetic resin, ceramic, metal, cloth, etc. The material constituting the other layers can be used alone or in combination. Among these, the material constituting the other layers is suitably at least one selected from synthetic resin and metal.

[0358] The synthetic resins that can be used in the laminated structure of the present embodiment include, for example, polar resins such as polyamide resins, polyurethane resins, polyester resins, polycarbonate resins, polyphenylene sulfide resins, polyacrylate resins, polymethacrylate resins, polyether resins, (meth) acrylonitrile-butadiene-styrene resins, (meth) acrylonitrile-styrene resins, (meth) acrylate-butadiene-styrene resins, (meth) acrylate-styrene resins, (meth) methyl acrylate-butadiene-styrene resins, epoxy resins, phenolic resins, diallyl phthalate resins, polyimide resins, melamine resins, polyacetal resins, polysulfone resins, polyethersulfone resins, polyetherimide resins, polyphenylene ether resins, polyarylate resins, polyetheretherketone resins, polystyrene resins, rubber-reinforced polystyrene resins, and syndiotactic polystyrene resins; and non-polar resins such as polyolefin resins. These synthetic resins can be used alone or in combination of two or more.

[0359] Examples of the polyamide resin include polyamide 6 (PA6) and polyamide 66 (PA66).

[0360] Examples of the polyolefin resin include polyethylene, polypropylene, polybutene-1, polyhexene-1, poly-3-methyl-butene-1, poly-4-methyl-pentene-1, copolymers of one or more of ethylene and α-olefins having 3 to 20 carbon atoms (e.g., propylene, 1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, 1-decene, 3-methyl-1-butene, 4-methyl-1-pentene, 6-methyl-1-heptene, isooctene, isooctadiene, decadiene, etc.), ethylene-propylene-diene copolymers (EPDM), ethylene-vinyl acetate copolymers, ethylene-acrylic acid copolymers, and the like.

[0361] In the layer formed by the synthetic resin, additives can be added as needed as long as the purpose of the present invention is not impaired. The additives include, for example, heat stabilizers, light stabilizers, ultraviolet absorbers, antioxidants, lubricants, colorants, antistatic agents, flame retardants, water repellents, waterproofing agents, hydrophilicity imparting agents, electrical conductivity imparting agents, thermal conductivity imparting agents, electromagnetic wave shielding imparting agents, light transmittance regulators, fluorescent agents, slip imparting agents, transparency imparting agents, anti-blocking agents, metal inertizing agents, antibacterial agents, etc.

[0362] The ceramics that can be used in the laminated structure of the present embodiment refer to non-metallic inorganic materials, and examples thereof include metal oxides, metal carbides, metal nitrides, etc. Examples thereof include glass, cement, aluminum oxide, zirconium oxide, zinc oxide-based ceramics, barium titanate, lead zirconate titanate, silicon carbide, silicon nitride, ferrite, etc.

[0363] The metals that can be used in the stacked structure of the present embodiment include, for example, iron, copper, aluminum, magnesium, nickel, chromium, zinc, and alloys thereof as components. As the metal that can be used in the stacked structure, it is preferably at least one selected from aluminum alloys and stainless steel. In addition, the layer formed by the metal can be a layer having a metal surface formed by plating such as copper plating, nickel plating, chromium plating, tin plating, zinc plating, platinum plating, gold plating, silver plating, etc.

[0364] The type of fabric that can be used in the laminate structure of the present embodiment is not particularly limited, and examples thereof include woven fabrics, knitted fabrics, felt, and nonwoven fabrics.

[0365] The raw material of the cloth may be natural fiber, synthetic fiber, or a combination of natural fiber and synthetic fiber. Although not particularly limited, natural fibers include cotton, silk, hemp, and wool.

[0366] In addition, as synthetic fibers, for example, polyester fibers, polyacrylonitrile fibers (polyacrylonitrile), polyurethane fibers, polyamide fibers, polyolefin fibers, and vinylon fibers can be listed. As polyamide fibers, nylon 6 and nylon 66 can be listed. As polyolefin fibers, polyethylene fibers and polypropylene fibers can be listed.

[0367] [Method for producing laminated structure]

[0368] The manufacturing method of the stacked structure of the present invention is not particularly limited, and is preferably manufactured by melt-stacking the resin composition of the present embodiment of the above-mentioned other materials. For example, molding methods such as injection insert molding, extrusion lamination, coextrusion molding, calendering molding, coagulation molding, compression molding, and melt injection molding can be listed.

[0369] For example, when a laminated structure is produced by injection insert molding, an adherend formed in advance into a predetermined shape and size is placed in a mold, and the resin composition of the present embodiment is injection-molded therein to produce the laminated structure.

[0370] When a laminated structure is produced by extrusion lamination, the resin composition of this embodiment in a molten state can be directly extruded from a die head having a predetermined shape and attached to an extruder onto the surface or edge of an adherend formed in advance into a predetermined shape and size, thereby producing a laminated structure.

[0371] When the laminated structure is produced by co-extrusion molding, the laminated structure may be produced by simultaneously extruding molten resin using two extruders.

[0372] When a laminated structure is produced by calendaring, the resin composition of this embodiment, which is melted by a heating roller, calendared and passed through a plurality of rollers to be in a molten state, is thermally welded to the surface of an adherend formed in advance into a predetermined shape and size, thereby producing a laminated structure.

[0373] When the laminated structure is manufactured by a pressure molding method, a molded body comprising the resin composition of the present invention is pre-molded by injection molding or extrusion molding, and the molded body is heated and pressurized until the adherend is pre-formed into a predetermined shape and size using a pressure molding machine, etc. This molding method is particularly suitable when the adherend is ceramic or metal.

[0374] As a molding method based on melt lamination molding, injection insert molding is preferable.

[0375] In particular, the laminated structure of the present embodiment is preferably produced by insert molding the resin composition into a layer formed of a material other than the resin composition, more preferably by insert molding the resin composition at a resin temperature of 160 to 250°C.

[0376] From the viewpoint of obtaining sufficient adhesive strength, the injection molding temperature in the injection insert molding method is preferably 180° C. or higher, more preferably 200° C. or higher. From the viewpoint of being able to achieve both tensile properties and strong adhesive strength and preventing the color of the resin composition from deteriorating due to high temperature, the injection molding temperature is preferably 240° C. or lower, more preferably 230° C. or lower.

[0377] In the resin composition of the present embodiment, especially when a thermoplastic polyurethane resin is used as the resin (B), the resin composition is prone to hue change, tensile properties, etc. deterioration due to high temperature. In the past, in order to obtain adhesive strength, the resin composition constituting the adhesive layer needs to be injection-insert molded at a high temperature exceeding 250°C, and thus, hue change, tensile properties, etc. deterioration are prone to occur. On the other hand, when the conventional resin composition is injection-insert molded at a temperature below 250°C, sufficient adhesive strength cannot be obtained.

[0378] However, the resin composition of the present embodiment can exhibit strong adhesive force and suppress deterioration of hue change, tensile properties, etc. in the resin composition by injection molding preferably at a resin temperature of 160 to 250° C., thereby more significantly exerting the effect of the present invention. It should be noted that the resin temperature during injection molding can be appropriately set as long as the effect of the present invention is not excessively impaired.

[0379] In addition, when the adherend is a synthetic resin, both can be melted at the same time and co-extruded or co-injected. In addition, one can be molded in advance and melt-coated thereon, or solution coating can be performed. In addition, two-color molding, insert molding, etc. can also be used.

[0380] <Purpose>

[0381] The resin composition of the present embodiment can be widely used in various applications. For example, as an example, a laminated structure used by bonding the resin composition of the present embodiment to various housing materials can be listed. The raw materials of the above-mentioned housing materials usually use light metals such as aluminum and magnesium alloys in addition to synthetic resins and synthetic resins containing glass fibers. As a preferred embodiment, the above-mentioned housing materials can be listed as housing materials of electronic and electrical equipment, OA equipment, household electrical appliances, sporting goods, power tools, automotive components, etc. More specifically, a preferred embodiment is a large display, a notebook personal computer, a portable phone, a portable information terminal, an electronic dictionary, a video camera, a digital camera, a portable recording player, a converter and a power tool, etc. The resin composition of the present embodiment is bonded to these housing materials, so as to be used as a laminated structure. In the above-mentioned laminated structure, the layer comprising the resin composition of the present embodiment can be preferably used as an impact mitigation material, a covering material with an anti-slip function, a waterproof material and a design material, etc.

[0382] In addition, in another preferred embodiment, the resin combination of the present embodiment is used as a sealing material. As the example of the above-mentioned sealing material, the sealing material of the joint in the molded body and the structure etc. of the transparent member represented by glass etc. can be listed. As the above-mentioned transparent member, it is also preferred to use the resin member of polycarbonate and PMMA etc. As the specific example of the joint of the molded body and the structure of the transparent member, the joint of the glass in the window of the building and the aluminum window frame, the joint of the glass in the automobile and the metal opening etc. and the joint of the glass and the metal frame in the solar cell module etc. can be illustrated. The resin combination of the present embodiment can be preferably used as the sealing material applied in the above-mentioned joint.

[0383] In another preferred embodiment, the resin composition of this embodiment can be preferably used as a separator of a secondary battery, etc. The separator of the secondary battery is not particularly limited, and preferably exemplified are various information terminal devices such as notebook personal computers, mobile phones, and cameras; separators of secondary batteries used in hybrid vehicles, fuel cell vehicles, etc.

[0384] Example

[0385] Hereinafter, the present invention will be specifically described with reference to Examples and Comparative Examples, but the present invention is not limited thereto.

[0386] It should be noted that β-farnesene (purity 97.6 mass %, manufactured by Amyris Inc.) was prepared by using The mixture was purified by using a molecular sieve of , and distilled under a nitrogen atmosphere to remove hydrocarbon impurities such as gingerol, bisabolene, farnesene epoxide, farnesol isomers, E,E-farnesol, squalene, ergosterol and various dimers of farnesene, and used for the following polymerization.

[0387] <Each ingredient>

[0388] The components used in Examples and Comparative Examples are as follows.

[0389] [Modified hydrogenated product (A)]

[0390] (A1) to (A4): modified hydrogenated products of Production Examples 1-1 to 1-4 described later

[0391] (A5): Maleic anhydride-modified ethylene-butene copolymer (trade name: Tafmer (registered trademark) MH5020, manufactured by Mitsui Chemicals, Inc., modification amount: 1.0 phr, melt flow rate: 1.2 g / 10 min (catalog value, ASTM D1238, 230° C.))

[0392] (A6): Maleic anhydride-modified polypropylene (trade name: ADMER (registered trademark) QF500, manufactured by Mitsui Chemicals, Inc., modification amount: 0.8 phr)

[0393] Among them, (A4), (A5) and (A6) are used as comparative examples.

[0394] [Resin (B)]

[0395] (B1): Thermoplastic polyurethane resin (trade name: Elastollan (registered trademark) C80A, manufactured by BASF Japan, Class A hardness: 80)

[0396] (B2) to (B4): acrylic block copolymers of Production Examples 2-1 to 2-4 described later

[0397] [Hydrogenated block copolymer (C)]

[0398] (C1) to (C5): hydrogenated block copolymers of Production Examples 3-1 to 3-5 described later

[0399] [Softener]

[0400] Softener: Paraffin-based process oil (trade name: DIANAPROCESS OIL PW-90, manufactured by Idemitsu Kosan Co., Ltd.)

[0401] [Antioxidant]

[0402] Hindered phenol antioxidant (trade name: ADEKASTAB AO-60, manufactured by ADEKA Corporation)

[0403] <Measurement method>

[0404] In addition, the details of each measurement method in the production examples are shown below.

[0405] (1) Polymer block content

[0406] [Modified hydrogenated product (A) and hydrogenated block copolymer (C)]

[0407] The contents of the polymer block (A-1) and the polymer block (C-1) are measured as follows.

[0408] The modified hydrogenated product (A) and the hydrogenated block copolymer (C) were dissolved in CDCl3, respectively. 1 The content of the polymer block is calculated from the ratio of the peak area derived from styrene to the peak area derived from isoprene and / or butadiene or the ratio of the peak area derived from styrene to the peak area derived from farnesene by H-NMR measurement [apparatus: "AVANCE400 Nanobay" (manufactured by Bruker Corporation), measurement temperature: 30°C].

[0409] [Resin (B): acrylic block copolymer]

[0410] The contents of the polymer block (E1) and the polymer block (D1) constituting the acrylic block copolymer are determined by 1 H-NMR measurement [apparatus: nuclear magnetic resonance apparatus "JNM-ECX400" (manufactured by JEOL Ltd.), measurement temperature: 30°C, deuterated solvent: deuterated chloroform] was performed and calculated as follows. The mass ratio (E1) / (D1) was calculated from the calculated contents of the polymer block (E1) and the polymer block (D1).

[0411] exist 1 In the H-NMR spectrum, the signals near 3.6ppm and 3.7ppm are attributed to the ester group (-O-CH3) of the methyl methacrylate unit and the ester group (-O-CH3) of the methyl acrylate unit, respectively, and the signal near 4.0ppm is attributed to the ester group (-O-CH2-CH2-CH2-CH3) of the n-butyl acrylate unit or the ester group (-O-CH2-CH(-CH2-CH3)-CH2-CH2-CH2-CH3) of the 2-ethylhexyl acrylate unit. The molar ratio of each monomer unit is obtained from the ratio of these integrated values, and the content of each polymer block is calculated by converting it into a mass ratio based on the molecular weight of the monomer unit.

[0412] (2) Weight average molecular weight

[0413] [Modified hydrogenated product (A) and hydrogenated block copolymer (C)]

[0414] The weight average molecular weights of the polymer block (A-1), the polymer block (A-2), the polymer block (C-1), the polymer block (C-2), the modified hydrogenated product (A) and the hydrogenated block copolymer (C) were measured as follows.

[0415] The polystyrene-equivalent weight average molecular weight (Mw) of the modified hydrogenated product (A) and the hydrogenated block copolymer (C) was determined by gel permeation chromatography (GPC) measurement under the following conditions.

[0416] The weight average weight (Mw) of each polymer block was determined by measuring a sampled liquid by GPC measurement under the following conditions every time the polymerization of each polymer block was completed in the production process.

[0417] <GPC measurement apparatus and measurement conditions>

[0418] ·Equipment: GPC equipment "HLC-8020" manufactured by Tosoh Corporation

[0419] Separation columns: Two "TSKgel G4000HX" manufactured by Tosoh Corporation were connected in series.

[0420] ·Eluent: Tetrahydrofuran

[0421] Eluent flow rate: 0.7mL / min

[0422] Sample concentration: 5mg / 10mL

[0423] Column temperature: 40°C

[0424] Detector: Differential refractive index (RI) detector

[0425] Standard curve: Prepared using standard polystyrene

[0426] [Resin (B): acrylic block copolymer]

[0427] The peak top molecular weight (Mp) and molecular weight distribution (Mw / Mn) of the acrylic block copolymer are determined by measuring the molecular weight in terms of standard polystyrene using gel permeation chromatography (GPC) under the following GPC conditions.

[0428] <GPC measurement apparatus and measurement conditions>

[0429] ·Equipment: GPC equipment "GPC8020" manufactured by Tosoh Corporation

[0430] Separation columns: "TSKgel GMHXL", "G4000HXL" and "G5000HXL" manufactured by Tosoh Corporation were connected in series.

[0431] ·Eluent: Tetrahydrofuran

[0432] Eluent flow rate: 1.0mL / min

[0433] Sample concentration: 5mg / 10mL

[0434] Column temperature: 40°C

[0435] Detector: "RI-8020" manufactured by Tosoh Corporation

[0436] Standard curve: Prepared using standard polystyrene

[0437] (3) Hydrogenation rate

[0438] The hydrogenation rates of the modified hydrogenated product (A) and the hydrogenated block copolymer (C) were measured as follows.

[0439] The modified hydrogenated product (A) before modification and the hydrogenated block copolymer (C) before and after hydrogenation were dissolved in CDCl3, respectively. 1H-NMR measurement [apparatus: "AVANCE400 Nanobay" (manufactured by Bruker Corporation), measurement temperature: 30°C].

[0440] The hydrogenation rate of the carbon-carbon double bond in the structural unit derived from the conjugated diene compound in the modified hydrogenated product (A) and the hydrogenated block copolymer (C) before modification was calculated by the following formula from the peak of the proton in the carbon-carbon double bond appearing at 4.5 to 6.0 ppm in the obtained spectrum.

[0441] Hydrogenation rate of the modified hydrogenated product (A) before modification (mol %) = {1-(the number of moles of carbon-carbon double bonds contained in the modified hydrogenated product (A) before modification) / (the number of moles of carbon-carbon double bonds contained in the modified hydrogenated product (A) before hydrogenation and before modification)}×100

[0442] Hydrogenation rate of hydrogenated block copolymer (C) (mol %) = {1-(the number of moles of carbon-carbon double bonds contained per 1 mole of hydrogenated block copolymer (C)) / (the number of moles of carbon-carbon double bonds contained per 1 mole of hydrogenated block copolymer (C) before hydrogenation)}×100

[0443] The calculated hydrogenation rate of the modified hydrogenated product (A) before modification is shown in Table 2 as "Hydrogenation rate in polymer block (A-2) (mol %)". The calculated hydrogenation rate of the hydrogenated block copolymer (C) is shown in Table 5 as "Hydrogenation rate in polymer block (C-2) (mol %)".

[0444] In addition, the hydrogenation rate did not change before and after the modification.

[0445] (4) Vinyl bonding amount

[0446] The vinyl bond amounts of the polymer blocks (A-2) and (C-2) were measured as follows.

[0447] The modified hydrogenated product (A) before hydrogenation and the hydrogenated block copolymer (C) before hydrogenation were dissolved in CDCl3, respectively. 1 H-NMR measurement [apparatus: "AVANCE400 Nanobay" (manufactured by Bruker Corporation), measurement temperature: 30°C].

[0448] In the case of (A1) to (A4), (C1), (C3), and (C4), the vinyl bond content (total content of 3,4-bonded units and 1,2-bonded units) is calculated from the ratio of the peak area corresponding to the 3,4-bonded unit and the 1,2-bonded unit in the isoprene structural unit and the 1,2-bonded unit in the butadiene structural unit to the total peak area of ​​the structural units derived from isoprene and / or butadiene.

[0449] In the case of (C2), the vinyl bond amount is calculated from the ratio of the peak area corresponding to the 3,13-bonded unit and the 1,2-bonded unit in β-farnesene to the total peak area of ​​the structural unit derived from β-farnesene.

[0450] In the case of (C5), the vinyl bond amount is calculated from the ratio of the peak area corresponding to the 1,2-bonded unit in the butadiene structural unit to the total peak area of ​​the structural unit derived from isoprene and / or butadiene, and the ratio of the peak area corresponding to the 3,13-bonded unit and the 1,2-bonded unit in β-farnesene to the total peak area of ​​the structural unit derived from β-farnesene.

[0451] (5) (Melt flow rate (MFR))

[0452] The flow rate (g / 10 minutes) of the modified hydrogenated product (A) was measured using a melt indexer under the conditions of a temperature of 230° C. and a load of 21 N in accordance with JIS K 7210:2014.

[0453] (6) Glass transition temperature

[0454] The glass transition temperatures of the modified hydrogenated product (A) and the hydrogenated block copolymer (C) are measured as follows.

[0455] The measurement was performed using a DSC measuring apparatus (DSC6200 manufactured by Hitachi High-Technologies Corporation) at a temperature range of -100°C to +350°C and a heating rate of 20°C / min, and the inflection point temperature of the baseline shift due to the glass transition was defined as the glass transition temperature.

[0456] (7) tanδ peak temperature and tanδ peak intensity

[0457] The tan δ peak top temperature and tan δ peak top intensity of the modified hydrogenated product (A) and the hydrogenated block copolymer (C) were measured as follows.

[0458] Using a press molding device "NF-50T" (manufactured by Shinto Metal Industries, Ltd.), the modified hydrogenated product (A) and the hydrogenated block copolymer (C) were pressurized for 3 minutes at a temperature of 230°C and a pressure of 10 MPa, thereby preparing a sheet with a thickness of 1.0 mm. The sheet was cut into a circular plate shape with a diameter of 8 mm as a test piece.

[0459] As a measuring device, according to JIS K7244-10:2005, a strain-controlled dynamic viscoelasticity device, i.e., a rotational rheometer "ARES-G2" (manufactured by TA Instruments) was used. The above-mentioned test piece was clamped on a flat plate with a diameter of 8 mm, and vibration was applied under the conditions of a strain of 0.1% and a frequency of 1 Hz. The test was carried out by raising the temperature from -70°C to 120°C at 3°C / min.

[0460] Through the above test, the temperature at which the maximum peak intensity can be obtained (peak top temperature) and the maximum peak intensity of tan δ (peak top intensity) are obtained.

[0461] (8) Maleic anhydride modification amount (functional group content (phr))

[0462] After 5 g of the modified hydrogenated product (A) was dissolved in 180 ml of toluene, 20 ml of ethanol was added, and the mixture was titrated with a 0.1 mol / L potassium hydroxide solution. The modified amount was calculated using the following calculation formula.

[0463] Maleic anhydride modification amount (phr) = titration amount × 5.611 / sample amount × 98 × 100 / 56.11 × 1000

[0464] <Production Example>

[0465] [Production Example 1-1]

[0466] Modified hydride (A1)

[0467] (1) Hydrogenated block copolymer

[0468] Into a nitrogen-purged and dried pressure vessel were added 50 kg of cyclohexane (solvent) dried over molecular sieve A4 and 0.07 kg of a 10.5 mass % sec-butyllithium cyclohexane solution as an anionic polymerization initiator (actual amount of sec-butyllithium added: 7.4 g).

[0469] After the temperature in the pressure vessel was raised to 50°C, 1.00 kg of styrene (first time) was added and polymerized for 60 minutes, then the temperature was lowered to 40°C, 0.033 kg of 2,2-di(2-tetrahydrofuryl)propane (DTHFP) as a Lewis base was added, and a mixed solution of 8.17 kg of isoprene and 6.49 kg of butadiene was added over 5 hours, and polymerized for 2 hours. Thereafter, the temperature was raised to 50°C, 1.00 kg of styrene (second time) was added, and polymerized for 30 minutes, and methanol was added to stop the reaction, thereby obtaining a reaction solution containing a triblock copolymer of polystyrene-poly(isoprene / butadiene)-polystyrene.

[0470] A Ziegler catalyst (Al / Ni Ziegler catalyst) composed of nickel octoate and trimethylaluminum was added to the reaction solution under a hydrogen atmosphere, and the reaction was carried out for 5 hours under the conditions of a hydrogen pressure of 1 MPa and 80° C. The reaction solution was naturally cooled and the pressure was released, and then the Ziegler catalyst was removed by washing with water, and the reaction solution was vacuum dried to obtain a hydrogenated product of a triblock copolymer of polystyrene-poly(isoprene / butadiene)-polystyrene.

[0471] (2) Modified hydride

[0472] The extrusion was carried out using a twin-screw extruder "ZSK26mc" manufactured by Coperion under the following extrusion conditions ( L / D=56), 10 kg of the above-obtained hydride, 0.01 kg of 2,5-dimethyl-2,5-di(tert-butylperoxy)hexane (PERHEXA 25B-40, manufactured by NOF Corporation) as a free radical initiator, and 0.1 kg of maleic anhydride as a modifier were mixed and made into a molten state, and a modification reaction was carried out to obtain a modified hydride (A1).

[0473] The components and their amounts are shown in Table 1. Table 2 also shows the results of the above-mentioned physical property evaluations.

[0474] [Production Examples 1-2 to 1-4]

[0475] Modified hydride (A2)~(A4)

[0476] Modified hydrogenated products (A2) to (A4) were obtained in the same manner as in Production Example 1 except that the components and their amounts were changed as shown in Table 1. Table 2 shows the results of the above-mentioned physical property evaluations.

[0477] [Production Example 2-1]

[0478] Acrylic block copolymer (B2)

[0479] (Step 1) To a pressure vessel that had been purged with nitrogen and dried was added 50.0 kg of toluene and 0.0998 kg of 1,2-dimethoxyethane while stirring at room temperature (23° C.), followed by the addition of 0.820 kg of a toluene solution containing 412 mmol of isobutylbis(2,6-di-tert-butyl-4-methylphenoxy)aluminum, and further, 0.121 kg of a cyclohexane solution containing 206 mmol of sec-butyllithium.

[0480] (Step 2) Then, 1.47 kg of methyl methacrylate was added thereto at room temperature with stirring, and stirring was continued for 60 minutes. The reaction liquid was initially yellow, but turned colorless after stirring for 60 minutes.

[0481] (Step 3) Thereafter, the internal temperature of the polymerization liquid was cooled to -30°C, and 6.33 kg of n-butyl acrylate was added dropwise over 4 hours with stirring. After the completion of the dropwise addition, stirring was continued at -30°C for further 5 minutes.

[0482] (Step 4) Thereafter, 1.20 kg of methyl methacrylate was added thereto, and the mixture was stirred at room temperature overnight.

[0483] (Step 5) After adding 0.370 kg of methanol to stop the polymerization reaction, the obtained reaction solution was poured into methanol under stirring to precipitate a white precipitate. The obtained white precipitate was recovered and dried to obtain an acrylic block copolymer (B2).

[0484] Table 3 shows the components and their amounts used, and the results of the above-mentioned physical property evaluations.

[0485] [Production Examples 2-2 to 2-4]

[0486] Acrylic block copolymers (B3) and (B4)

[0487] Acrylic block copolymers (B3), (B4) and (B5) were obtained in the same manner as in Production Example 2-1 except that the components and their amounts were changed as shown in Table 3. Table 3 shows the results of the above-mentioned physical property evaluations.

[0488] [Production Example 3-1]

[0489] Hydrogenated block copolymer (C1)

[0490] Into a nitrogen-purged and dried pressure vessel were added 50 kg of cyclohexane (solvent) dried over molecular sieve A4 and 0.03 kg of a 10.5 mass % sec-butyllithium cyclohexane solution as an anionic polymerization initiator (actual amount of sec-butyllithium added: 3.2 g).

[0491] After the temperature in the pressure vessel was raised to 50° C., 1.32 kg of styrene (first time) was added and polymerized for 60 minutes, and then a mixed solution of 3.44 kg of isoprene and 2.73 kg of butadiene was added over 5 hours and polymerized for 2 hours. Thereafter, 1.32 kg of styrene (second time) was added and polymerized for 60 minutes, and methanol was added to terminate the reaction, thereby obtaining a reaction solution containing a triblock copolymer of polystyrene-poly(isoprene / butadiene)-polystyrene.

[0492] A Ziegler catalyst (Al / Ni Ziegler catalyst) composed of nickel octoate and trimethylaluminum was added as a hydrogenation catalyst to the reaction solution under a hydrogen atmosphere, and the reaction was carried out for 5 hours under the conditions of a hydrogen pressure of 1 MPa and 80° C. The reaction solution was naturally cooled and the pressure was released, and then the Ziegler catalyst was removed by washing with water, and the reaction solution was vacuum dried to obtain a hydrogenated block copolymer (C1) of a triblock copolymer of polystyrene-poly(isoprene / butadiene)-polystyrene.

[0493] The components and their amounts are shown in Table 4. Table 5 also shows the results of the above-mentioned physical property evaluations.

[0494] [Production Examples 3-2 and 3-3]

[0495] Hydrogenated block copolymers (C2), (C3)

[0496] Hydrogenated block copolymers (C2) and (C3) were obtained in the same manner as in Production Example 3-1 except that the components and their amounts were changed as shown in Table 4. Table 5 shows the results of the above-mentioned physical property evaluations.

[0497] [Production Example 3-4]

[0498] Hydrogenated block copolymer (C4)

[0499] Into a nitrogen-purged and dried pressure vessel were added 50 kg of cyclohexane (solvent) dried over molecular sieve A4 and 0.10 kg of a 10.5 mass % sec-butyllithium cyclohexane solution as an anionic polymerization initiator (actual amount of sec-butyllithium added: 10.5 g).

[0500] After the temperature in the pressure vessel was raised to 50° C., 1.67 kg of styrene (first time) was added and polymerized for 60 minutes, the temperature in the vessel was lowered to 40° C., 0.29 kg of tetrahydrofuran as a Lewis base was added, 13.33 kg of isoprene was added over 5 hours, and polymerization was carried out for 2 hours. Thereafter, the temperature was raised to 50° C., 1.67 kg of styrene (second time) was added, and polymerization was carried out for 60 minutes, and methanol was added to terminate the reaction, thereby obtaining a reaction solution containing a triblock copolymer of polystyrene-polyisoprene-polystyrene.

[0501] A Ziegler catalyst (Al / Ni-based Ziegler catalyst) composed of nickel octoate and trimethylaluminum was added as a hydrogenation catalyst to the reaction solution under a hydrogen atmosphere, and the reaction was carried out for 5 hours under the conditions of a hydrogen pressure of 1 MPa and 80° C. After the reaction solution was naturally cooled and the pressure was released, the Ziegler catalyst was removed by washing with water, and the reaction solution was vacuum dried to obtain a hydrogenated block copolymer (C4) of a triblock copolymer of polystyrene-polyisoprene-polystyrene.

[0502] The components and their amounts are shown in Table 4. Table 5 also shows the results of the above-mentioned physical property evaluations.

[0503] [Production Example 3-5]

[0504] Hydrogenated block copolymer (C5)

[0505] Into a nitrogen-purged and dried pressure vessel were placed 50 kg of cyclohexane as a solvent, 227 g of a 10.5 mass % sec-butyllithium cyclohexane solution as an anionic polymerization initiator (actual amount of sec-butyllithium added: 23.9 g), and 100 g of tetrahydrofuran as a Lewis base.

[0506] After the temperature in the pressure vessel was raised to 50° C., 7.4 kg of β-farnesene was added and polymerized for 2 hours, then 3.0 kg of styrene (first time) was added and polymerized for 1 hour, and then 4.6 kg of butadiene was added and polymerized for 1 hour. Then, 100 g of phenyl benzoate as a coupling agent was added to the polymerization reaction solution, and the reaction was allowed to react for 1 hour, thereby obtaining a reaction solution containing a poly(β-farnesene)-polystyrene-polybutadiene-polystyrene-poly(β-farnesene) pentablock copolymer.

[0507] A Ziegler hydrogenation catalyst composed of nickel octoate and trimethylaluminum was added to the reaction solution under a hydrogen atmosphere, and the mixture was reacted for 5 hours under the conditions of a hydrogen pressure of 1 MPa and 80° C. The reaction solution was naturally cooled and the pressure was released, and the catalyst was removed by washing with water, and the mixture was vacuum dried to obtain a hydrogenated product (C5) of a poly(β-farnesene)-polystyrene-polybutadiene-polystyrene-poly(β-farnesene) pentablock copolymer.

[0508] The components and their amounts are shown in Table 4. Table 5 also shows the results of the above-mentioned physical property evaluations.

[0509] [Table 1]

[0510] Table 1

[0511]

[0512] [Table 2]

[0513] Table 2

[0514] Modified hydride (A) A1 A2 A3 A4 Structural units of polymer block (A-1) St St St St Components constituting polymer block (A-2) Ip / Bd Ip / Bd ID B Mass ratio of components constituting polymer block (A-2) 55 / 45 55 / 45 100 100 Molar ratio of components constituting polymer block (A-2) 50 / 50 50 / 50 100 100 Polymer structure (bonding method) A-1 / A-2 / A-1 A-1 / A-2 / A-1 A-1 / A-2 / A-1 A-1 / A-2 / A-1 Content of polymer block (A-1) (mass %) 12 12 12 20 Weight average molecular weight of polymer block (A-1) 8,300 8,300 6,700 5,000 Weight average molecular weight of polymer block (A-2) 208,000 208,000 143,000 77,000 Weight average molecular weight of modified hydrogenated product (A) 185,000 185,000 154,000 87,000 Hydrogenation rate in polymer block (A-2) (mol %) 97 97 91 99 Vinyl bond content in polymer block (A-2) (mol%) 78 78 83 40 Maleic anhydride modification amount (phr) 0.40 0.87 0.40 1.70 MFR_230℃, 21N(g / min) 12.2 15.5 20.8 5.0 Glass transition temperature(℃) 4 4 20 -56 tanδ peak temperature (℃) 14.0 14.0 33.2 -46.4 tanδ peak intensity 2.10 2.10 2.09 0.42 Weight average molecular weight of modified hydride 187,000 187,000 156,000 88,500

[0515] [Table 3]

[0516]

[0517] The expressions in Table 3 are as follows.

[0518] MMA-nBA-MMA: methyl methacrylate polymer block-butyl acrylate polymer block-methyl methacrylate polymer block

[0519] MMA-(nBA / MA)-MMA: methyl methacrylate polymer block-(n-butyl acrylate / methyl acrylate) copolymer block-methyl methacrylate polymer block

[0520] [Table 4]

[0521] Table 4

[0522]

[0523] [Table 5]

[0524]

[0525] <Examples 1 to 14 and Comparative Examples 1 to 3>

[0526] (1) Preparation of resin composition

[0527] The components and their amounts were used as shown in Table 6 or Table 7. The premixed composition was melt-kneaded using a twin-screw extruder ("ZSK26Mc" manufactured by Coperion; number of barrels: 14) at 230°C and a screw speed of 200 rpm to obtain a resin composition. The properties of the obtained resin composition were evaluated by the following method. The evaluation results are shown in Table 6 or Table 7.

[0528] (2) Fabrication of laminated structure

[0529] A laminated structure was produced by injection insert molding using the following adherend (length 100 mm×width 35 mm×thickness 1 mm) as an insert component.

[0530] When the adherend was a synthetic resin, both surfaces of the adherend were wiped with gauze soaked with methanol to perform degreasing and then naturally dried.

[0531] When the adherend is a metal, both surfaces of the adherend are washed with an aqueous surfactant solution and distilled water in this order, and dried at 100°C.

[0532] Each adherend pre-treated as described above is fixed to the mold using a vacuum line. Under the conditions of a mold temperature of 50°C and a barrel temperature of 230°C, the obtained resin composition is filled into the mold, and the surface temperature of the adherend is cooled to 50°C, thereby obtaining a stacked structure. For the obtained stacked structure, the adhesive force (peel strength) of the resin composition is evaluated according to the following method. The evaluation results are shown in Table 6 or Table 7.

[0533] In addition, the details of the adherend for producing the laminated structure are as follows.

[0534] Polycarbonate (PC) sheet: Trade name "UPILON S-3000R", manufactured by Mitsubishi Engineering-Plastics Corporation

[0535] Acrylonitrile butadiene styrene resin (ABS) sheet: trade name "TOYOLAC 700-314", manufactured by Toray Industries

[0536] Nylon 6 (PA6) sheet: Trade name "UBENylon61013B", manufactured by Ube Industries

[0537] Aluminum alloy (AL) plate: material "A5052P"

[0538] <Evaluation method>

[0539] The details of each evaluation method in Examples and Comparative Examples are shown below.

[0540] [Melt flow rate (MFR)]

[0541] The resin compositions obtained in Examples and Comparative Examples were measured for outflow rate (g / 10 minutes) at a temperature of 230° C. and a load of 21 N using a melt indexer in accordance with JIS K7210:2014.

[0542] In addition, since the melt flow rate of Comparative Example 2 was less than 0.1 g / 10 min and difficult to measure, it was expressed as “<0.1” in Table 6.

[0543] [Hardness and tensile properties]

[0544] (1) Film production

[0545] The resin compositions obtained in the examples and comparative examples were injection molded using an injection molding machine ("EC75SX; 75 tons" manufactured by Toshiba Machine Co., Ltd.) at a cylinder temperature of 230°C and a mold temperature of 50°C to produce sheets having a length of 100 mm, a width of 35 mm, and a thickness of 2 mm.

[0546] (2) Hardness

[0547] A dumbbell No. 3 type test piece was obtained from the sheet obtained above using a punching blade in accordance with JIS K 6251:2010.

[0548] Three obtained test pieces were stacked to a thickness of 6 mm, and the values ​​immediately after measurement (0 seconds), 3 seconds after measurement, and 15 seconds after measurement were obtained by the type A hardness tester method of JIS K 6253-2:2012.

[0549] There is a tendency that as the change in the measured value over time increases, good flexibility, elasticity, and mechanical strength are more likely to be obtained, and strong adhesive force is more likely to be exhibited.

[0550] (3) Tensile properties

[0551] The 100% modulus, tensile breaking strength, and tensile breaking elongation of the dumbbell No. 3 test piece obtained above were measured in accordance with JIS K 6251:2010.

[0552] The 100% modulus, tensile strength at break, and tensile elongation at break are all such that the higher the numerical value of the measurement result, the better the tensile property.

[0553] [Adhesion (peel strength)]

[0554] The laminated structures obtained in the examples and comparative examples were subjected to a peel test using INSTRON 5566 manufactured by INSTRON Corporation in accordance with JIS K6854-2:1999 at a peel angle of 180° and a tensile speed of 200 mm / min to measure the peel strength. The peel strength was calculated as an average value of four times.

[0555] The higher the peel strength value, the higher the adhesion to the adherend.

[0556] [Table 6]

[0557]

[0558] [Table 7]

[0559]

[0560] The "content ratio of the component (A)" in Tables 6 and 7 refers to the content ratio (mass %) of the modified hydrogenated product (A) in 100 mass % of the resin composition.

[0561] In Table 6, if Examples 1 to 3, which differ only in the type of modified hydrogenated product (A), are compared with Comparative Examples 1 to 3, it can be seen that Examples 1 to 3 show excellent flexibility and molding processability, and excellent tensile properties. It can also be seen that Examples 1 to 3 have higher peel strength for aluminum, specifically, aluminum alloys, than Comparative Examples 1 to 3. Therefore, it can be seen that Examples 1 to 3 show strong adhesion to both synthetic resins and metals even when injection molding is performed at a low temperature of about 230°C. In addition, according to Example 4, it can be seen that even if two or more hydrogenated block copolymers (C) are used, the tensile properties are excellent, and strong adhesion is shown to both synthetic resins and metals.

[0562] It can be seen from Table 7 that Examples 5 to 14 show excellent flexibility and molding processability, and excellent tensile properties. It can also be seen that even when Examples 5 to 14 are injection molded at a low temperature of about 230°C, they show strong adhesion to both synthetic resins and metals. In addition, according to Example 13, it can be seen that even if two or more hydrogenated block copolymers (C) are used, excellent tensile properties and strong adhesion can be obtained. In addition, according to Example 14, it can be seen that the resin composition can obtain excellent tensile properties and strong adhesion by containing a modified hydrogenated product (A) and a resin (B).

[0563] <Examples 15 to 18>

[0564] (1) Preparation of resin composition

[0565] The components and their amounts were used as shown in Table 8, and the premixed composition was melt-kneaded using the aforementioned twin-screw extruder "ZSK26Mc" at 230°C and a screw speed of 200 rpm to obtain a resin composition. The properties of the obtained resin composition were evaluated by the following methods. The evaluation results are shown in Table 8.

[0566] (2) Fabrication of laminated structure

[0567] A laminated structure was produced by injection insert molding using the following adherend (length 100 mm×width 35 mm×thickness 1 mm) as an insert component. The adherend was prepared by pre-treating in the same manner as above.

[0568] Each adherend was fixed to the mold using a vacuum line. Under various conditions of a mold temperature of 50°C and a barrel temperature of 230°C and 250°C, the obtained resin composition was filled into the mold, and the surface temperature of the adherend was cooled to 50°C, thereby obtaining a stacked structure. For the obtained stacked structure, the adhesive force (peel strength) of the resin composition was evaluated according to the following method. The evaluation results are shown in Table 8.

[0569] In addition, the details of the adherend for producing the laminated structure are as follows.

[0570] Polycarbonate (PC) sheet: Trade name "UPILON S-3000R", manufactured by Mitsubishi Engineering-Plastics Corporation

[0571] Acrylonitrile butadiene styrene resin (ABS) sheet: trade name "TOYOLAC 700-314", manufactured by Toray Industries

[0572] Polypropylene (PP) sheet: Trade name "Prime Polypro J106G", manufactured by Prime Polymer

[0573] Nylon 6 (PA6) sheet: Trade name "UBENylon61013B", manufactured by Ube Industries

[0574] Aluminum alloy (AL) plate: material "A5052P"

[0575] ·Stainless steel (SUS) plate: Material "SUS304"

[0576] <Evaluation method>

[0577] The details of each evaluation method in Examples and Comparative Examples are shown below.

[0578] [Melt flow rate (MFR)]

[0579] The outflow rate (g / 10 minutes) was measured by the same method and conditions as those described in the above section [Melt flow rate (MFR)].

[0580] [Hardness and tensile properties]

[0581] (1) Film production

[0582] The resin compositions obtained in Examples 15 to 18 were injection molded using the aforementioned injection molding machine "EC75SX" under various conditions of a mold temperature of 50°C and a barrel temperature of 230°C and 250°C to produce sheets of 100 mm in length, 35 mm in width and 2 mm in thickness.

[0583] (2) Hardness

[0584] A dumbbell No. 3 type test piece was obtained from the sheet obtained above using a punching blade in accordance with JIS K 6251:2010.

[0585] Three obtained test pieces were stacked to a thickness of 6 mm, and the values ​​immediately after measurement (0 seconds), 3 seconds after measurement, and 15 seconds after measurement were obtained by the type A hardness tester method of JIS K 6253-2:2012.

[0586] (3) Tensile properties

[0587] The 100% modulus, tensile breaking strength, and tensile breaking elongation of the dumbbell No. 3 test piece obtained above were measured in accordance with JIS K 6251:2010.

[0588] [Adhesion (peel strength)]

[0589] The laminated structures obtained in Examples 15 to 18 were subjected to a peel test using the aforementioned "INSTRON 5566" according to JIS K6854-2:1999 at a peel angle of 180° and a tensile speed of 200 mm / min to measure the peel strength. The peel strength was calculated as an average value of four times.

[0590] [Table 8]

[0591] Table 8

[0592]

[0593] The "content ratio of the component (A)" in Table 8 means the content ratio (mass %) of the modified hydrogenated product (A) in 100 mass % of the resin composition.

[0594] As shown in Table 8, Examples 15 to 18 exhibited sufficient tensile properties and strong adhesion to both synthetic resins and metals (e.g., aluminum alloys and stainless steel), and in particular, when injection molded at 250°C, there was a tendency for the adhesion to be improved. Therefore, it can be seen that Examples 15 to 18 exhibited excellent flexibility and molding processability even when injection molded at any temperature between 230°C and 250°C, and achieved both excellent tensile properties and strong adhesion.

[0595] <Examples 19 to 23 and Comparative Example 4>

[0596] (1) Preparation of resin composition

[0597] The components and their amounts were used as shown in Table 9, and the premixed composition was melt-kneaded using the twin-screw extruder "ZSK26Mc" at 230°C and a screw speed of 200 rpm to obtain a resin composition. The properties of the obtained resin composition were evaluated by the following methods. The evaluation results are shown in Table 9.

[0598] (2) Fabrication of laminated structure

[0599] A laminated structure was produced by injection insert molding using the following adherend (length 100 mm×width 35 mm×thickness 1 mm) as an insert component. The adherend was prepared by pre-treating in the same manner as above.

[0600] Each adherend was fixed to the mold using a vacuum line. Under the conditions of a mold temperature of 50°C and a barrel temperature of 230°C, the obtained resin composition was filled into the mold, and the surface temperature of the adherend was cooled to 50°C, thereby obtaining a stacked structure. For the obtained stacked structure, the adhesive force (peel strength) of the resin composition was evaluated according to the following method. The evaluation results are shown in Table 9.

[0601] In addition, the details of the adherend for producing the laminated structure are as follows.

[0602] Polycarbonate (PC) sheet: Trade name "UPILON S-3000R", manufactured by Mitsubishi Engineering-Plastics Corporation

[0603] Acrylonitrile butadiene styrene resin (ABS) sheet: trade name "TOYOLAC 700-314", manufactured by Toray Industries

[0604] Polypropylene (PP) sheet: Trade name "Prime Polypro J106G", manufactured by Prime Polymer

[0605] Nylon 6 (PA6) sheet: Trade name "UBENylon61013B", manufactured by Ube Industries

[0606] Aluminum alloy (AL) plate: material "A5052P"

[0607] ·Stainless steel (SUS) plate: Material "SUS304"

[0608] <Evaluation method>

[0609] The details of each evaluation method in Examples and Comparative Examples are shown below.

[0610] [Melt flow rate (MFR)]

[0611] The outflow rate (g / 10 minutes) was measured by the same method and conditions as those described in the above section [Melt flow rate (MFR)].

[0612] [Hardness and tensile properties]

[0613] (1) Film production

[0614] The resin compositions obtained in Examples 19 to 23 and Comparative Example 4 were injection molded using the aforementioned injection molding machine "EC75SX" at a mold temperature of 50°C and a barrel temperature of 230°C to produce sheets with a length of 100 mm, a width of 35 mm, and a thickness of 2 mm.

[0615] (2) Hardness

[0616] A dumbbell No. 3 type test piece was obtained from the sheet obtained above using a punching blade in accordance with JIS K 6251:2010.

[0617] Three obtained test pieces were stacked to a thickness of 6 mm, and the values ​​immediately after measurement (0 seconds), 3 seconds after measurement, and 15 seconds after measurement were obtained by the type A hardness tester method of JIS K 6253-2:2012.

[0618] (3) Tensile properties

[0619] The 100% modulus, tensile breaking strength, and tensile breaking elongation of the dumbbell No. 3 test piece obtained above were measured in accordance with JIS K 6251:2010.

[0620] [Adhesion (peel strength)]

[0621] The laminated structures obtained in Examples 19 to 23 and Comparative Example 4 were subjected to a peel test using the aforementioned "INSTRON 5566" according to JIS K 6854-2:1999 at a peel angle of 180° and a tensile speed of 200 mm / min to measure the peel strength. The peel strength was calculated as an average value of a total of four times.

[0622] [Table 9]

[0623] Table 9

[0624]

[0625] The "content ratio of the component (A)" in Table 9 refers to the content ratio (mass %) of the modified hydrogenated product (A) in 100 mass % of the resin composition.

[0626] As shown in Table 9, Examples 19 to 23 exhibited sufficient tensile properties and strong adhesion to both synthetic resin and metal (e.g., aluminum alloy and stainless steel). Comparative Example 4 did not exhibit strong adhesion to synthetic resin and metal (especially stainless steel) compared to Examples 19 to 23.

[0627] Industrial Applicability

[0628] The resin composition of the present embodiment has excellent tensile properties and has strong adhesion to synthetic resins and metals, etc. Therefore, the laminated structure to which the resin composition of the present embodiment is bonded can be used, for example, as an impact relief material, a covering material with an anti-slip function, a waterproof material, and a design material bonded to the outer shell of a large display, a notebook personal computer, a mobile phone, a portable information terminal, an electronic dictionary, a video camera, a digital camera, a portable recording player, a converter, an electric tool, and the like.

Claims

1. A resin composition comprising a modified hydrogenated product of a block copolymer (A) and a resin (B), wherein the modified hydrogenated product of the block copolymer (A) comprises a polymer block (A-1) and a polymer block (A-2), wherein the polymer block (A-1) has a structural unit derived from an aromatic vinyl compound, and the polymer block (A-2) has a structural unit derived from a conjugated diene compound, The modified hydrogenated product (A) has at least one functional group selected from a carboxyl group, an amino group, a hydroxyl group and a group derived from an acid anhydride, and the vinyl bond content of the polymer block (A-2) is 50 to 99 mol%. The resin (B) is at least one selected from an acrylic block copolymer and a thermoplastic polyurethane resin, The mass ratio (A) / (B) of the modified hydrogenated product (A) and the resin (B) is 90 / 10 to 10 / 90, The resin composition has a melt flow rate of 5 g / 10 minutes or more measured at a temperature of 230° C. and a load of 21 N in accordance with JIS K7210:2014.

2. The resin composition according to claim 1, further comprising a hydrogenated block copolymer (C), wherein the hydrogenated block copolymer (C) comprises a polymer block (C-1) and a polymer block (C-2), wherein the polymer block (C-1) comprises a structural unit derived from an aromatic vinyl compound, and the polymer block (C-2) comprises a structural unit derived from a conjugated diene compound.

3. The resin composition according to claim 2, wherein The vinyl bond content of the polymer block (C-2) is 1 to 85 mol%.

4. The resin composition according to claim 2 or 3, wherein The hydrogenation rate of carbon-carbon double bonds in the polymer block (C-2) is 80 to 100 mol %.

5. The resin composition according to any one of claims 2 to 4, wherein The conjugated diene compound in the polymer block (C-2) contains at least one selected from the group consisting of isoprene, butadiene and farnesene.

6. The resin composition according to any one of claims 2 to 5, wherein The content ratio of the polymer block (C-1) in the hydrogenated block copolymer (C) is 5 to 70% by mass.

7. The resin composition according to any one of claims 1 to 6, wherein The content of the functional group relative to the modified hydrogenated product (A) is 0.10 to 5.00 phr.

8. The resin composition according to any one of claims 1 to 7, wherein The hydrogenation rate of carbon-carbon double bonds in the polymer block (A-2) is 80 to 100 mol %.

9. The resin composition according to any one of claims 1 to 8, wherein The content ratio of the structural unit derived from isoprene in the polymer block (A-2) is 30% by mass or more.

10. The resin composition according to any one of claims 1 to 9, wherein The conjugated diene compound in the polymer block (A-2) contains isoprene and butadiene.

11. The resin composition according to any one of claims 1 to 10, wherein The content of the polymer block (A-1) in the modified hydrogenated product (A) is 5 to 40% by mass. 12 . The resin composition according to claim 2 , comprising 5 to 200 parts by mass of a softener based on 100 parts by mass of the hydrogenated block copolymer (C).

13. The resin composition according to claim 12, wherein The softener is at least one selected from paraffinic process oil, cycloparaffinic process oil and aromatic process oil.

14. A molded product comprising the resin composition according to any one of claims 1 to 13. 15 . A laminated structure comprising a layer formed from the resin composition according to claim 1 and a layer formed from a material other than the resin composition.

16. The laminated structure according to claim 15, wherein: The other material is at least one selected from synthetic resins and metals.

17. The method for producing a laminated structure according to claim 15 or 16, wherein: For the layer formed of other material than the resin composition, the resin composition is injection insert-molded.

Citation Information

Patent Citations

  • Acrylic terpolymer, its production method, and its application to elastomer product production

    JP1993507737A

  • Methacrylic block copolymer and its production

    JP1994093060A

  • Thermoplastic polymer composition

    JP1999302495A

  • Production of acrylic block copolymer

    JP1999335432A

  • Thermoplastic elastomer composition

    JP2003041089A